Nationwide surveillance of pESI-positive Salmonella Infantis ST32 in South Korea: Endemic establishment of a dominant lineage across the broiler production chain, 2020–2023 - Hee-Seung Kang; Md.Sekendar Ali; Bo-Youn Moon; Min Young Kim; Yu-Jeong Hwang; Ji-In Kim; Seung-Chun Park; Jae-Myung Kim; Suk-Kyung Lim (Food Microbiology, 2027)

Multivariate integration of physicochemical and targeted metabolite profiles with sensory data for the predictive modeling of taste intensities in fermented kimchi - In Min Hwang; Daun Kim; Seul-Gi Jeong; So Yeong Mun; Chang Hee Jeong; Jong-Hee Lee; Ho Myeong Kim (Food Research International, 2026)

Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Comprehensive metabolomic and quantitative analysis of Paeoniae Radix for characterization of chemical profiles and antioxidant properties - Choong-In Yun; Youngjae Shin; Min Jeong Kim; Young-Jun Kim (Food Bioscience, 2026)

Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Machine learning-based spatiotemporal modeling and health risk assessment of PAHs and metals in an industrial city - Jeong-Tae Ju; Sang-Jin Lee; In-Gyu Cho; Ji Yoon Choi; Taekyu Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Quadruple co-infection with Mycobacterium tuberculosis complex and M. kansasii in a chronically immunosuppressed cat - Sungyoung Choi; Soo-Nyun Choi; Tak Gyeom Lee; Sungweon Ryoo; Ji-Hoon Kwak; Kun-Woo Kim; Tae In Park; Woo-Jin Song; Eun-Joo Lee; Kyu-Shik Jeong (Veterinary Research Communications, 2026)

Polymer type drives successional structural and functional organization of plastisphere microbial networks - Kyu-Young Shim; In-Cheol Yeo; Euihyeon Lee; Hyun-Jung Kim; Kang Eun Kim; Jiezhang Mo; Youn-Jung Kim; Chang-Bum Jeong (Marine Environmental Research, 2026)

Allergenicity of edible insect proteins: Cross-reactivity, processing effects, and food safety considerations - Jae Hoon Lee; Ji Yoon Cha; Seonmin Lee; Yea-Ji Kim; Jeong-Heon Kim; Dong Hyun Keum; Hae In Yong; Min Hyeock Lee; Yun-Sang Choi (Food Chemistry, 2026)

Temporally programmed dual-function scaffold with simultaneous cellulose and calcium lactate regeneration for enhanced osteogenesis via lactate-induced OR5AN1 activation - Siphesihle Cassandra Nonjola; Jeong In Kim; Soonchul Lee (Carbohydrate Polymers, 2026)

Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Effects of Clinostat rotation on stem morphology of Pisum Sativum - Sang-Min Kim; Jung-Hoo Kook; Jeong-In Choi; Oluwasegun Moses Ogundele; Won-Cheol Lee; Hyeon-Tae Kim (Life Sciences in Space Research, 2026)

Magnetically self-assembled 3D Micro-pillar supercapacitor with high areal capacitance - Seongyeol Kim; In Hyeok Oh; Haebin Jeong; Suk Tai Chang (Chemical Engineering Journal, 2026)

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Heavy metals in carbonated waters and beverages on the South Korean market - Yongcheol Lee; Hyuny Clark-Shim; Min-Su Chang; In-Sook Lee; Yun-Jung Yi; Hyun-Jeong Kim (Food Additives & Contaminants Part B-Surveillance, 2026)

Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

High-Throughput Sequencing-Guided Development and Validation of an RT-dPCR Assay for Sensitive Detection of Lentinula edodes Spherical Virus in Shiitake Mushrooms - Min-Jae Kim; Chae-Min Kang; In-Gyeong Kim; Rae-Dong Jeong (Current Microbiology, 2026)

Size‐, sex‐ and site‐dependent morphological variation in the stone flounder ( Kareius bicoloratus ) from Korean coastal waters - Eun Jeong Kim; Songhyun Gwon; Ju Hwan Park; In Chul Bang; Yoon Kwon Nam (Journal of Fish Biology, 2026)
Kareius bicoloratus is a commercially important flatfish in Korean coastal fisheries and an ecologically relevant benthic species in nearshore ecosystems. To evaluate how multiple biological and environmental factors jointly shape flatfish morphology, we analysed 81 morphometric indices and two‐dimensional geometric morphometrics (GMM) in wild K. bicoloratus collected from two Korean coastal regions, incorporating size, sex and sampling site. Classical morphometrics based on a three‐way ANOVA framework identified body size and sex as the primary drivers of shape variation, particularly influencing surface area‐, depth‐ and angular traits, whereas geographic effects were more limited and context dependent. GMM analyses supported these patterns. Procrustes ANOVA detected significant shape effects of size, sex and site, and CVA revealed clear multivariate separation among groups, with Mahalanobis distances of 3.28–5.49 among sex groups and Procrustes distances of 0.032–0.049. Geographic divergence was also evident in GMM space, with Procrustes distances of 0.033–0.036 between sites. Allometry analyses indicated heterogeneous allometric trajectories for size and sex but not for site. Mitochondrial DNA analyses revealed moderate genetic differentiation between regions, and Mantel tests detected a weak but significant association between genetic and morphological distances. These findings provide a robust morphological baseline for K. bicoloratus .

Spatial heterogeneity of food web structure driven by glacial retreat in Marian Cove, Antarctica: linking environmental DNA interconnections - Kyu-Young Shim; In-Cheol Yeo; Jun-Oh Min; Jeong-Hoon Kim; Sun-Yong Ha; Chang-Bum Jeong (Marine Life Science & Technology, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Integrative Transcriptome and GWAS Analyses Reveal Growth-Associated Molecular Architecture in Pacific Abalone (Haliotis discus hannai) - Hyejung Jung; Eun Soo Noh; Hyejin Kim; Hee-Bok Park; Young-Su Seo; In Jun Hwang; Hee Jeong Kong; Jung-Ha Kang; Jungwook Park (Fishes, 2026)
Pacific abalone (Haliotis discus hannai) is a widely cultured and economically important abalone species in aquaculture yet improving growth performance remains a major challenge for stable production. To clarify the molecular architecture associated with growth performance in Pacific abalone, we integrated transcriptome and genome-wide association study (GWAS) data from high-growth and low-growth groups showing significant growth differences. Transcriptome profiles from hepatopancreas and mantle tissues were used to construct a co-expression network of 43,125 genes, summarized into 22 modules associated with tissue specificity and growth-related variation. In parallel, analysis of a custom 60K SNP array identified 67 significant growth-associated SNPs. Integration of these GWAS signals into the co-expression network revealed a core module most strongly correlated with growth index and enriched for SNP-derived candidate genes. Functional enrichment indicated that the core module was associated with proteostasis and growth-related signaling pathways, including insulin, Ras, and MAPK signaling. Protein–protein interaction analysis further identified 11 hub genes with high intramodular connectivity and direct interactions with SNP-derived genes, most of which participate in receptor-mediated and intracellular growth-regulatory functions. These findings provide an integrated molecular framework for growth performance in Pacific abalone and candidate targets for future molecular breeding strategies.

Interaction between ethanol and flunitrazepam in rats: Pharmacokinetic mechanisms and toxicological implications - Yejin Kim; Jeong In Seo; Jin Ah Won; Sooyeun Lee; Hye Hyun Yoo (Chemico-Biological Interactions, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Development of a Two-Set Multiplex PCR System for Rapid Discrimination of Seven Commercially Important Cuttlefish Species Using COI-Derived SNP Markers - Chun Mae Dong; Mi-Nan Lee; Hee Jeong Park; Hyo Sun Jung; Eun Soo Noh; In Joon Hwang; Jung-Ha Kang; Eun-Mi Kim (Fishes, 2026)
Reliable identification of seafood species is critical for fisheries management and product authentication, especially when morphological characteristics are lost during processing. In this study, a multiplex PCR system was developed to distinguish seven cuttlefish species (six Sepia spp. and Sepiella inermis) commercially distributed in the Korean seafood market. Species identity was first confirmed by amplifying a mitochondrial cytochrome c oxidase subunit I (COI) fragment (~658 bp) using universal primers (LCO1490/HCO2198), showing 99–100% sequence similarity to corresponding GenBank reference sequences. Analysis of genetic variation based on a 530 bp aligned region demonstrated complete interspecific differentiation without shared haplotypes among species. The number of haplotypes per species ranged from 5 to 21, with haplotype diversity values between 0.667 and 1.000. An extended COI fragment (~1200 bp) was further analyzed to identify diagnostic interspecific variation for marker development. Seven diagnostic single-nucleotide polymorphism (SNP) sites were identified and used to design species-specific forward primers with diagnostic nucleotides positioned at the 3′ termini. Distinct amplicons (220–1099 bp) were generated and clearly resolved by agarose gel electrophoresis. Because simultaneous amplification of all seven primer pairs reduced amplification efficiency, the assay was divided into two multiplex sets. Under optimized conditions (56 °C), each species produced a single expected band without cross-amplification. This multiplex PCR system provides a rapid and sequencing-free approach for reliable species discrimination and can be effectively applied to fisheries monitoring and seafood authentication in commercial supply chains.

Unveiling uncertainty in microplastic quantification: Artificial intelligence integrated Raman analysis - Min Young Oh; In-Chun Jeong; Kihyun Kim; Jeein Hong; Minseon Ju; Jaebum Choo; Ji-Hyun Kim; Sungguan Hong (Journal of Hazardous Materials, 2026)

Psychrotrophic lactic acid bacteria enhance microbial safety in kimchi: Evidence from untargeted metabolomics - Daun Kim; In Min Hwang; Ho Myeong Kim; Seul-Gi Jeong; Hae Woong Park (International Journal of Food Microbiology, 2026)

Structural degradation of kraft lignin under long-term UV irradiation: Molecular, spectroscopic, and surface-level insights - Chaeeun Kim; Chaewoo Jeong; Jungkyu Kim; In-Gyu Choi; Hyo Won Kwak (Biomass and Bioenergy, 2026)

Probiotic-Derived Strain-Specific Metabolites Ameliorate Metabolic Dysfunction–Associated Steatotic Liver Disease through Modulation of the Gut-Liver Axis - Sang Jun Yoon; Jieun Choi; Sung-Min Won; Jeong Seok Yu; Hee Young Kim; Hyun Chae Joung; In Gyu Park; Jung A Eom; Sang Hak Han; Do Yup Lee; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

RNAseq-based molecular insights into three insecticide resistances in Laodelphax striatellus: Structural perspective on CYP6ER2 in detoxification - Minyoung Choi; Murtaza Khan; In-hong Jeong; Juil Kim (Pesticide Biochemistry and Physiology, 2026)

Nuclear receptor ERR contributes to imidacloprid resistance by upregulating cytochrome P450 in Nilaparvata lugens - Woo-Ram Park; Byungyoon Choi; Nanthini Sadasivam; Hui-Jin Bae; Sunmin Kim; Eunae Kim; Hueng-Sik Choi; In-Hong Jeong; Don-Kyu Kim (Insect Biochemistry and Molecular Biology, 2026)

Digital-twin tool for a drinking water distribution system using augmented reality and EPANET - Ji-Ye Park; Kwang-Ju Kim; Minhyuk Jeung; In-Su Jang; Jung-Won Yu; Mi-Seon Kang; Hyun-Su Bae; Changyoon Jeong; Sang-Soo Baek (Environmental Modelling & Software, 2026)

Achieving BT.2020 red emission with narrowband deep-red iridium complexes in OLEDs - Gyeong Seok Lee; Woo Jin Jeong; Huanyu Zhou; Hyun-Wook Kim; Da In Kim; Kwan-Nyeong Kim; Dong-Hyeok Kim; Thi Na Le; Seungyeon Cho; Jongchan Kim; Tae-Woo Lee; Yun-Hi Kim (Chemical Engineering Journal, 2026)

A single urine test-based SERS–AI–BAM for on-site multiple cancer diagnosis and metabolite profiling - Hyo Jeong Seo; Jun Young Kim; Vo Thi Nhat Linh; Boyou Heo; Jun-Young Yang; Rowoon Park; In Woong Han; Sung-Gyu Park; Min-Young Lee; Samjin Choi; Ho Sang Jung (Chemical Engineering Journal, 2026)

GelMA Hydrogel/Alginate-Based Scaffolds: 3D Bioprinting for Cartilage Tissue Engineering - Tae Hyung Kim; Young Sam Kim; In Kyong Shim; Woo Shik Jeong (Tissue Engineering and Regenerative Medicine, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Precursor feeding strategy of oxydifficidin production in submerged culture of Bacillus velezensis 8–2 and its biological control potential against soft rot disease - Seulbi Kim; Ho Myeong Kim; In Min Hwang; Seul-Gi Jeong; Chang Hee Jeong; Jin-Cheol Kim; Hae Woong Park (Pesticide Biochemistry and Physiology, 2026)

Broad-host-range bacteriophages CBP1 and CBP2 with dual-species activity against Campylobacter jejuni and Campylobacter coli - Eunbyeol Ahn; Jinshil Kim; Joonbeom Kim; Jeong In Hur; Sangryeol Ryu; Byeonghwa Jeon (International Journal of Food Microbiology, 2026)

Flame-constructed spinel Fe-Ni-O nanoparticles-on-nanosheet superstructures for scalable and durable hydrogen production - Jin Sil Kim; Sung Won Hwang; Yoo Jae Jeong; Runfa Tan; Ha Min Lee; Arumugam Sivanantham; In Sun Cho (Chemical Engineering Journal, 2026)

Enhancing CO2-to-CH4 conversion efficiency of TiO2 through synergistic morphology tuning, defect engineering, and heterojunction formation - Dongyun Kim; Kyuseok Lee; Young Ho Park; Junho Lee; Jeonghyeon Lee; Chaelin Shin; Hyeonjong Jeong; Chang-Hee Cho; G. Murali; Seung Jun Lee; Insik In; Su-Il In (Chemical Engineering Journal, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Disturbance of benthic topography and macrofauna community by sand mining in EEZ of the South Sea of Korea - Dong-U Kim; Changkeun Lee; Su In Kim; Seong Woon Jeong; Taeha Kim; Eun Pyo Lim; Soonwoo Lee; Soonyoung Wang; Seong Eun Kim; Jong Seong Khim; Ho Kyung Ha (Regional Studies in Marine Science, 2025)

Effects of mineral resources on the growth of the harmful algal species Microcystis aeruginosa: From screening to understanding the underlying mechanisms - Hyeonjung Yu; So-Jeong Kim; Jungho Ryu; Dong-Wan Cho; In-Hyun Nam (Journal of Environmental Management, 2025)

Integrated VOC and non-VOC profiling for stage-specific quality assessment of kimchi fermentation using LC-MS/MS and GC-IMS - Ji Young Jeong; Min Ji Kim; Hyun-Sung Kim; Jong-Hee Lee; In Min Hwang (Food Chemistry, 2025)

Serine protease–viscoelastic polysaccharide interaction in inorganic CaCO3: Enhanced thermal stability for efficient enzyme particulation via immobilization - Soyoon Baek; Chan Hee Lee; Dain Kim; Jinhee Jeong; In Ki Hong; Seunghee Bae; Ee Taek Hwang (Carbohydrate Polymers, 2025)

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Modulating kimchi taste and fermentation with Latilactobacillus sakei, Leuconostoc mesenteroides, and Weissella koreensis starters - So Yeong Moon; Chang Hee Jeong; In Min Hwang; Daun Kim; Mo Eun Lee; Seul-Gi Jeong; Ho Myeong Kim (Food Research International, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

Vacancy-modulated vertical heterojunction for high-performance self-driven photodetectors - Go-Eun Kim; Mi-Jeong Kim; Tae In Kim; Hyuck-In Kwon; Ick-Joon Park (Chemical Engineering Journal, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

Development of a feedback-regulated temperature control system to enable supercooling reversion in beef preservation - Seokhyeon Yun; Taeho Kim; In-U Jeong; Song-Yi Choi; Soyeon Kim; Jin Hong Mok; Taiyoung Kang (Innovative Food Science & Emerging Technologies, 2025)

Transcriptomic analysis revealed the adaptations of Latilactobacillus sakei to the cold conditions of kimchi fermentation - Min Ji Kim; Ji Young Jeong; Hyun-Sung Kim; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Research International, 2025)

Compact and cost-effective autofluorescence sensor for real-time environmental biofilm monitoring - In Ho Kim; Jae Hak Shin; Sang Bin Jeong; Gi Byoung Hwang; Chul Woo Park; Jae Hee Jung (Environmental Research, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Calcium-Rich Steel Slag as a Reactive Capping Material: Effects on Hydraulic Conductivity and Nutrient Attenuation in Cohesive Intertidal Sediments - Hee-Eun Woo; Valianto Rojulun Afif; Seongsik Park; Maheshkumar Prakash Patil; Ilwon Jeong; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Journal of Marine Science and Engineering, 2025)
Fine-grained intertidal sediments are typically characterized by low hydraulic conductivity and high nutrient loads, conditions that hinder biogeochemical recovery and exacerbate eutrophication. This study examined the feasibility of calcium-rich steel slag (SS) as a multifunctional capping material for improving both physical and chemical properties of cohesive sediments. Short-term (24 h) column experiments with two slag dosages (25 g and 50 g) revealed that the higher dosage (SS50) increased sediment hydraulic conductivity by 113.2%, likely through Ca2+-mediated flocculation and enhanced pore connectivity. Phosphate (PO4-P) in pore water decreased by up to 64.1%, and effluent dissolved inorganic nitrogen (DIN) declined by 62.8%, indicating combined effects of Ca-driven precipitation, adsorption, and enhanced flushing. However, SS addition also raised pore water pH (to 11.8) and lowered redox potential, leading to transient phosphate release at the effluent boundary under reducing conditions. Cation analysis confirmed Ca2+ stability and Na+ reduction, suggesting improved sediment structural integrity. The results suggest that steel slag is a promising reactive capping material capable of enhancing permeability and controlling nutrient release in cohesive coastal sediments, yet further investigation into long-term ecological effects and dosage optimization is necessary.

Physiological Effects of Suspended Solids on Venerupis philippinarum and Argopecten irradians - Ha-Jeong Son; Ju-Won Kim; Min-Young Sohn; Chae-yeong Ji; Su Bhin Jeong; In Gu Kim; Jung-Ha Kang; Hee Jeong Kong; Chan-Il Park; Gyoungsik Kang (Fishes, 2025)
Suspended solids are small particles transported in the water column, which can damage marine ecosystems and impair the health of aquatic organisms. This study evaluated the physiological responses of clams (Venerupis philippinarum) and Atlantic Bay scallops (Argopecten irradians) to suspended solid exposure. Four concentrations (100–1000 mg/L) were tested, with a control group maintained at 0 mg/L. At each time point (1, 2, 4, 6, 8, and 12 days), hemolymph samples were collected from five individuals per group to measure GOT, GPT, ALP, and cortisol. Exposure to suspended solids significantly increased these biochemical indicators compared with the control. Quantitative survival analysis showed that Venerupis philippinarum survival declined to 83.3% (25/30) at 500 mg/L and 76.7% (23/30) at 1000 mg/L after 5 days, while the control maintained 100% survival. In Argopecten irradians, survival remained close to 100% in most treatments, with a slight reduction to 83.3% (25/30) at 1000 mg/L. No mortality occurred in the control group without suspended solids, whereas mortality was evident under combined temperature stress and suspended solid exposure. These findings demonstrate that suspended solids induce stress responses in both species, with early mortality in Venerupis philippinarum likely caused by particle adhesion to the gills, leading to reduced respiratory efficiency.

Visible light-driven selective redirection of phenolic carbon in heterogeneous Fenton-like reaction - Youn-Jun Lee; Prakash Govindaraj; Yoo Jae Jeong; Runfa Tan; In Sun Cho; Seong-Jik Park; Hern Kim; Chang-Gu Lee; Pedro J.J. Alvarez (Water Research, 2025)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Improved thermal stability of NbCoSn half-Heusler compounds via Sb doping-induced complementary point defect evolution - Kyuseon Jang; Poulumi Dey; Biswanath Dutta; Hail Park; Ji-Hee Son; Jeong-In Jang; Mohammed Kamran Bhat; Hanhwi Jang; Hyungsub Kim; Jungwoo Choi; Siyuan Zhang; Ruben Bueno Villoro; et al. (Chemical Engineering Journal, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Revealing the Prokaryotic Microbial Community Structures and their Ecological Potentials in Manjanggul Cave, a Lava Tube on Jeju Island - Minji Kim; So-Jeong Kim; In-Tae Cha; Soo-Je Park (Current Microbiology, 2025)

Evaluating ripeness in post-harvest stored kiwifruit using VIS-NIR hyperspectral imaging - Jeong-Eun Lee; Min-Jee Kim; Bo-Yeong Lee; Lee Jong Hwan; Ha-Eun Yang; Moon S. Kim; In Geun Hwang; Cheon Soon Jeong; Changyeun Mo (Postharvest Biology and Technology, 2025)

Garlic as a modulator of bacterial dynamics and metabolite profiles in kimchi fermentation - Min Ji Kim; Sera Jung; Hyun-Sung Kim; Ji Young Jeong; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Bioscience, 2025)

Evaluating the immunomodulation effects of live lactic acid bacteria from kimchi on Transwell Caco-2 monolayer permeability - Jin Yong Kang; Daun Kim; So Yeong Mun; Ji Young Jeong; Namhee Kim; In Min Hwang; Ho Myeong Kim (Food Bioscience, 2025)

Immunomodulation Effects of Porcine Cartilage Acellularized Matrix (pCAM) for Osteoarthritis Treatment - Ji Seob Kim; Hyeon Jae Kwon; In Sun Hwang; Young Hwa Lee; Kyung-Noh Yoon; Hee-Woong Yun; Jae-Hyeok Jang; Seo Jeong Kim; Zhoodatova Aiana; Seungwoo Kim; Minhee Moon; Bongki Kim; et al. (Tissue Engineering and Regenerative Medicine, 2025)

Multi-Enzyme Supplementation to Diets Containing 2 Protein Levels Affects Intramuscular Fat Content in Muscle and Modulates Cecal Microflora Without Affecting the Growth Performance of Finishing Pigs - Qianqian Zhang; Sungbo Cho; Junho Song; Jinuk Jeong; Minjae Yu; Seyoung Mun; Kyudong Han; In Ho Kim (Probiotics and Antimicrobial Proteins, 2025)

Root-Zone Cooling Effects on Growth, Physiological, and Biochemical Responses of Taraxacum coreanum Under Hydroponics - Min-Ji Kang; Seong-Nam Jang; In-Je Kang; Gyu-Sik Yang; Yun Gon Son; Jeong Yoon Kim; Eiji Goto; Ki-Ho Son (Journal of Plant Growth Regulation, 2025)

Spatial variations in organic matter sources and biogeochemical processes in the East Sea - Jiyoung Choi; Bo-Yeon Yi; Yuri Kim; Eun-Je Jeong; In-Kwon Um (Frontiers in Marine Science, 2025)
In this study, the spatial variations in total organic carbon (TOC), stable carbon isotopes (δ¹³Corg), C/N ratios, and nitrogen isotopes (δ¹⁵Norg) in East Sea sediments are examined to elucidate the sources, preservation, and diagenetic processes of organic matter. To this end, surface sediment samples were collected from the coastal regions of the East Sea using a box corer and analyzed for TOC, TON, stable isotopes (δ¹³C, δ¹⁵N), and grain size. The study region is categorized into three zones based on sediment characteristics: Zone A (straits), Zone B (northern coastal regions), and Zone C (central Ulleung Basin). Zone A, characterized by coarse sediments and dynamic hydrodynamic conditions, exhibits the lowest TOC (0.67%) and enriched δ¹³Corg values (-20.67‰). Zone B, influenced by coastal inputs, has moderate TOC (2.09%), slightly depleted δ¹³Corg (-21.09‰), and higher C/N ratios (6.30). Zone C, dominated by fine-grained mud sediments, features slightly lower TOC (1.96%), along with the most depleted δ¹³Corg (-21.86‰). Stable isotope analyses reveal that autochthonous particulate organic matter (POM) from marine phytoplankton is the primary source of organic matter in the East Sea. δ¹³Corg values (-23.15‰ to -20.33‰) align with phytoplankton-derived POM (-25‰ to -22‰), highlighting significant marine primary production contributions. In contrast, allochthonous inputs from atmospheric deposition, the Tsushima Warm Current, and rivers contribute approximately 82 gC/m²/year compared to 273 gC/m²/year from autochthonous sources. Seasonal δ¹³C variations are strongly correlated with peaks in primary productivity during spring and autumn. The study reveals differences between coastal (Zone B) and offshore (Zone C) regions in productivity regimes, nutrient utilization, and depositional settings. Coastal regions with high productivity show enriched δ¹³Corg, while offshore areas preserve isotopically lighter organic matter owing to stable depositional environments. Understanding the biogeochemical processes in the East Sea is essential for elucidating carbon cycling and its ecosystem implications. As a marginal sea with unique sedimentary dynamics, the East Sea serves as a natural laboratory for studying organic matter preservation. The findings provide insights into past and present carbon cycling and support predictions of future environmental changes under shifting climatic conditions.

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

RNA-seq-based identification of imidacloprid resistance mechanisms in Nilaparvata lugens and development of diagnostic tools for the CYP6ER1 variant - Minyoung Choi; Murtaza Khan; Changhee Han; In-hong Jeong; Nakjung Choi; Juil Kim (Pesticide Biochemistry and Physiology, 2025)

Modulation of fermentation dynamics in kimchi using Leuconostoc mesenteroides starter - Min Ji Kim; Ji Young Jeong; In Min Hwang; Jong-Hee Lee (Food Bioscience, 2025)

Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Jong Hee Kim; Jeong-In Park; Yewon Kim; Mira Park; Jang Kyun Kim; Young-Seok Han; Youn-Jung Kim (Ocean Science Journal, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

One-pot modular nanogel platform utilizing phenolic gelatin-polyethyleneimine for small RNA delivery - Kyoungmin Park; Jie Zheng; Jeong-Eun Yoo; Jonggun Kim; In-Yong Kim; Seungkwon You (Chemical Engineering Journal, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Reducing Healing Period with DDM/rhBMP-2 Grafting for Early Loading in Dental Implant Surgery - Jeong-Kui Ku; Jung-Hoon Lim; Jung-Ah Lim; In-Woong Um; Yu-Mi Kim; Pil-Young Yun (Tissue Engineering and Regenerative Medicine, 2025)
Background: Traditionally, dental implants require a healing period of 4 to 9 months for osseointegration, with longer recovery times considered when bone grafting is needed. This retrospective study evaluates the clinical efficacy of demineralized dentin matrix (DDM) combined with recombinant human bone morphogenetic protein-2 (rhBMP-2) during dental implant placement to expedite the osseointegration period for early loading. Methods: Thirty patients (17 male, 13 female; mean age 55.0 ± 8.8 years) requiring bone grafts due to implant fixture exposure (more than four threads; ≥ 3.2 mm) were included, with a total of 96 implants placed. Implants were inserted using a two-stage protocol with DDM/rhBMP-2 grafts. Early loading was initiated at two months postoperatively in the mandible and three months in the maxilla. Clinical outcomes evaluated included primary and secondary stability (implant stability quotient values), healing period, bone width, and marginal bone level assessed via cone-beam computed tomography. Results: All implants successfully supported final prosthetics with a torque of 50Ncm, without any osseointegration failures. The average healing period was 69.6 days in the mandible and 90.5 days in the maxilla, with significantly higher secondary stability in the mandible (80.7 ± 6.7) compared to the maxilla (73.0 ± 9.2, p < 0.001). Histological analysis confirmed new bone formation and vascularization. Conclusion: DDM/rhBMP-2 grafting appears to significantly reduce the healing period, enabling early loading with stable and favorable clinical outcomes.

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Single oral toxicity assessment and phytochemical analysis of the Ficus erecta Thunb. Leaves extract - Yu Jin Kim; Mee-Young Lee; Hyun Ji Park; Eunjin Sohn; Woo-Young Jeon; Sae-Rom Yoo; In Suk Choi; Joo-Hwan Kim; Soo-Jin Jeong (Toxicon, 2025)

Introducing Cu2O (111) phase on Cu(OH)2 nanorods integrated Pd-cocatalyst for boosting acetone selectivity via photoelectrochemical CO2RR - Periyayya Uthirakumar; Dasom Kim; Vandung Dao; Chen Kai; Changmin Yun; Youn Jeong Jang; In-Hwan Lee (Environmental Research, 2025)

Detection of the jellyfish Chrysaora pacifica by RPA-CRISPR-Cas12a environmental DNA (eDNA) assay and its evaluation through field validation and comparative eDNA analyses - Kyuhyeong Kim; Usha Jyoti Maji; Kyu-Young Shim; In-Cheol Yeo; Chang-Bum Jeong (Science of The Total Environment, 2024)

Role of Rab proteins in PFOA-induced changes in boar sperm motility and capacitation - Seung-Ik Jang; Jae-Hwan Jo; Claudine Uwamahoro; Eun-Ju Jung; Woo-Jin Lee; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Joonho Moon; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

Genetic dissection of resistance to Phytophthora sojae using genome-wide association and linkage analysis in soybean [Glycine max (L.) Merr.] - Hee Jin You; Ik Hyun Jang; Jung-Kyung Moon; In-Jeong Kang; Ji-Min Kim; Sungtaeg Kang; Sungwoo Lee (Theoretical and Applied Genetics, 2024)

Lelliottia wanjuensis sp. nov. Isolated from Korean Lettuce in Wanju, South Korea - Jiyeon Lee; Eewon Tai; Sunyoung Jeong; Ile Kim; Bo-Eun Kim; Myeong-In Jeong; Kwang-Kyo Oh; Natalia Biere; Charles M. A. P. Franz; Gyu-Sung Cho (Current Microbiology, 2024)
Ten Gram stain-negative, oxidase-negative, catalase-positive, rod-shaped strains were isolated from lettuce in the city Wanju in South Korea. Comparative 16S rRNA gene analysis and multilocus sequence analysis indicated that the strains grouped closely together with all other Lelliottia ( L .)-type strains. The average nucleotide identity (ANI) comparisons of the isolates showed a high relationship between the strains, as the ANI values of all strains ranged from 91.01 to 91.31% when compared to the L. jeotgali- type strain PFL01 T . All isolates showed the highest genomic DNA sequence similarity to the L. jeotgali PFL01 T strain at 43.3% when compared with digital DNA–DNA hybridization (dDDH). Strain V104_15 T of the proposed novel Lelliottia species showed 91.2% and 43.3% similarity with the most closely related L. jeotgali PFL01 T -type strain in the ANI and dDDH comparisons, respectively. Strain V104_15 T could not grow at 45 °C and 7% NaCl, while L. jeotgali PFL01 T strain could grow at both these conditions. Strain V104_15 T showed ß -glucosidase activity but not α-glucosidase activity, while the L. jeotgali PFL01 T strain was α -glucosidase positive but ß-glucosidase negative. The major cellular fatty acids of strain V104_15 T were C 16:0 and cyclo-C 17:0 including summed features. The mol % G + C content of the genomic DNA of strain V104_15 T was 55.74%. Phenotypic and biochemical characteristics, as well as the phylogenomic analysis indicated that the strain V104_15 T represents a novel species of the genus Lelliottia , for which the name Lelliottia wanjuensis sp. nov. is proposed. The type strain is V104_15 T (= LMG 32996 T = DSM 115585 T ).

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Distribution coefficient prediction using multimodal machine learning based on soil adsorption factors, XRF, and XRD spectrum data - Seongyeon Na; Heewon Jeong; Ilgook Kim; Seok Min Hong; Jaegyu Shim; In-Ho Yoon; Kyung Hwa Cho (Journal of Hazardous Materials, 2024)

Nationwide evaluation of microplastic properties in municipal wastewater treatment plants in South Korea - Jae-Ho Lee; So-Jeong Cheon; Chang-Soo Kim; Soo-Hyun Joo; Ki-In Choi; Dong-Hwan Jeong; Soo-Hyung Lee; Jeong-Ki Yoon (Environmental Pollution, 2024)

Combined water electrolysis and 2D hydron separator for enhanced hydrogen isotope separation - Chan Woo Park; Euna Jeong; Ilgook Kim; Hyung-Ju Kim; Hee-Man Yang; Young-Ho Sihn; In-Ho Yoon (Chemical Engineering Journal, 2024)

Olaparib synergically exacerbates the radiation-induced intestinal apoptosis in mice - Sohee Jeong; Jeongmin Lee; Jun Hong Park; Yeonghoon Son; Hae-June Lee; Changjong Moon; In Sik Shin; Joong Sun Kim; Sohi Kang (Molecular & Cellular Toxicology, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Ultrathin Two-Dimensional Ordered Porous Carbon Host with Atomically Dispersed Electrocatalytic Sites toward High Volumetric Energy Lithium-Sulfur Battery - Won-Gwang Lim; Minkyeong Ban; Kyu In Shim; Jinkyu Park; Seongbeen Kim; Seongseop Kim; Seoa Kim; Cheol-Young Park; Jeong Woo Han; Jinwoo Lee (Chemical Engineering Journal, 2024)

Design and Simulation-Based Validation of an AI Model for Predicting Grab-Type Ship Unloader Operation Data - Ga-Eun Jung; Woo-Hee Jeong; Seok-Ju Lee; Jae-In Lee; Tae-Won Kim; Hae-Jin Sung (Journal of Marine Science and Engineering, 2024)
Along with seaports automation, there is growing interest in the automation of Grab-Type Ship Unloader (GTSU) that unloads coal and iron ore from bulk carriers. Autonomous unloading operations of GTSU offer the potential for significant productivity improvement and cost savings. In this paper, an AI model trained with manual operation data was designed for GTSU automation operation, and the AI model was verified through the equation-of-motion-based GTSU operation simulator. The operation data of hoist, grab, and trolley were predicted by training the designed AI model with the manual operation data of GTSU. Before applying the predicted data to the actual equipment, the predicted driving data was verified using the equation-of-motion-based GTSU operation simulator. The AI prediction model was designed using the Multi-Layer Perception network, a type of artificial neural network. The AI prediction model was evaluated with the Mean-Squared Error indicator, and the validation loss was found to be less than 0.02. In addition, verification of the prediction data was performed using the GTSU dynamics-based simulator. The Mean Relative Error was up to 0.50, and the R2 score value exceeded 0.92, indicating that the model is effective in predicting operation data. The proposed AI prediction model will be effectively utilized to implement a fully automated unloading system.

Exploratory data analysis of the correlation between bioactive components in various tea extracts and the digestive function in vitro - Kang-Woo Lee; In-Su Na; Dong-Ho Lee; Jin-Woo Kim; Na-Yeon Lee; Jin-Oh Chung; Hyun Woo Jeong; Jonghee Sohn; Wan-Gi Kim; Soon-Mi Shim (Food Bioscience, 2024)

Carboxymethyl cellulose-based rotigotine nanocrystals-loaded hydrogel for increased transdermal delivery with alleviated skin irritation - Jun Soo Park; Jae Hee Seo; Min Young Jeong; In Gyu Yang; Ji Seong Kim; Jin Hwan Kim; Myoung Jin Ho; Sung Giu Jin; Min Koo Choi; Yong Seok Choi; Myung Joo Kang (Carbohydrate Polymers, 2024)

Mutational analysis of pig tissue factor pathway inhibitor α to increase anti-coagulation activity in pig-to-human xenotransplantation - Chang-Hee Lee; Hyeon Jeong Lee; Si-Won Park; Jiyoon Shin; Seok-Jin Kang; In-Byung Park; Hyun Kyung Kim; Taehoon Chun (Biotechnology Letters, 2024)

Relationship between rheological properties, sensory perception, and overall acceptability of thickened liquids for dysphagia in young and old healthy individuals - Yong Gi Chun; Yun Jeong Kim; In Young Lee; Eun Young Jeon; Bum-Keun Kim (Food Research International, 2024)

Coupled engineering strategy of CYB2 deletion and ACS1 overexpression improves cellulosic lactic acid production by Saccharomyces cerevisiae - Suhyeung Kim; Deokyeol Jeong; Byeungkwan Jang; Sujeong Park; Eun Joong Oh; In Jung Kim; Soo Rin Kim (Biomass and Bioenergy, 2024)

Highly visible-light-active sulfur and carbon co-doped TiO2 (SC-TiO2) heterogeneous photocatalysts prepared by underwater discharge plasma - Ha-Rim An; Chaehun Lim; Chung Gi Min; Byoungchul Son; Chang-Yeon Kim; Ji-In Park; Jong Pil Kim; Yesul Jeong; Jiwon Seo; Moonsang Lee; Jihyang Park; Young-Seak Lee; et al. (Chemosphere, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Flower-like Ti(HPO4)2 bioceramic-laden 3D printed platform for enhanced bone regeneration via BMP signaling pathway - Il Won Suh; Jeong In Kim; Bishnu Kumar Shrestha; Se Rim Jang; Chan Hee Park (Chemical Engineering Journal, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Enhanced solar-driven thermoelectric power generation and water desalination via hydrothermally synthesized degenerately doped copper selenide nanocrystals composited with polydimethylsiloxane - Keerthnasre Dhandapani; Hossein Fattahimoghaddam; In Ho Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Physicochemical characterization and environmental stability of a curcumin-loaded Pickering nanoemulsion using a pea protein isolate-dextran conjugate via the Maillard reaction - Yun Jeong Kim; Hae In Yong; Yong Gi Chun; Bum-Keun Kim; Min Hyeock Lee (Food Chemistry, 2024)

Combination approach of paired starter culture and lactic acid on inhibiting autochthonous lactic acid bacteria for extending kimchi shelf life - Chang Hee Jeong; Hye In Ko; Mo Eun Lee; Sung-Gi Min; Mi-Ai Lee; Tae-Woon Kim (Food Control, 2024)

High-performance interfacial water evaporation of black TiO2-x with high-concentration bulk oxygen vacancies - Myeongjun Ji; Jeong Hyun Kim; Hee Yeon Jeon; Seungheon Han; Dong Hoon Lee; Young-In Lee (Chemical Engineering Journal, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Bioconversion of citrus waste into mucic acid by xylose-fermenting Saccharomyces cerevisiae - Deokyeol Jeong; Sujeong Park; Grace Evelina; Suhyeung Kim; Heeyoung Park; Je Min Lee; Sun-Ki Kim; In Jung Kim; Eun Joong Oh; Soo Rin Kim (Bioresource Technology, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Ecological impacts of dam construction on epilithic diatom communities in estuaries: A case study of the Korean peninsula - Ha-Kyung Kim; In-Hwan Cho; Eun-A Hwang; Young-Hyo Kim; Jeong-Suk Moon; Bae-Kyung Park; Baik-Ho Kim (Ocean & Coastal Management, 2024)

Perfluorooctanoic acid suppresses sperm functions via abnormal Protein Kinase B activation during capacitation - Seung-Ik Jang; Jae-Hwan Jo; Eun-Ju Jung; Woo-Jin Lee; Ju-Mi Hwang; Jeong-Won Bae; Sangsu Shin; Sang In Lee; Myoung Ok Kim; Woo-Sung Kwon (Reproductive Toxicology, 2024)

Characterization of naturally occurring radioactive material dynamics in community water systems using groundwater from Ganghwa Island, Republic of Korea - Eunhyung Lee; Do-Hwan Jeong; Youn-Tae Kim; Inkyu Shin; Yu-Yeon Jeong; Jeong-In Kim; Minkyeong Lee; Hyun-koo Kim; Soo-Hyung Lee; MoonSu Kim (Journal of Hydrology, 2024)

TRIAD method to assess ecological risks of contaminated soils in abandoned mine sites - Dokyung Kim; Jin Il Kwak; Tae-Yang Lee; Lia Kim; Haemi Kim; Sun Hwa Nam; Wonjae Hwang; June Wee; Yong Ho Lee; Songhee Kim; Ji-In Kim; Sunhee Hong; et al. (Journal of Hazardous Materials, 2024)

Cold tolerance in Campylobacter jejuni and its impact on food safety - Jeong In Hur; Jinshil Kim; Mi Seon Kang; Hyun Jung Kim; Sangryeol Ryu; Byeonghwa Jeon (Food Research International, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Diesel particulate matter aggravates cyclophosphamide-induced testicular toxicity in mice via elevating oxidative damage - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; Yea-Gin Yang; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2024)

Delineation of LNAPL plumes in a clay-rich site in Gyeongsangnam-do Province, South Korea: integration of geophysical survey data with borehole data and soil sampling information - Bitnarae Kim; In Seok Joung; Huieun Yu; Juyeon Jeong; Seo Young Song; Jeong-sul Son; Youngchul Yu; Jehyun Shin; Ho Young Jo; Man Jae Kwon; Myung Jin Nam (Environmental Monitoring and Assessment, 2024)

Performance comparison of photodynamic antimicrobial chemotherapy with visible-light-activated organic dyes: Rose bengal, crystal violet, methylene blue, and toluidine blue O - Jae Hak Shin; Sang Bin Jeong; In Ho Kim; Seung Yeon Lee; Gi Byoung Hwang; Inyong Park; Ki Joon Heo; Jae Hee Jung (Environmental Research, 2023)

Maximizing clean hydrogen release from perhydro-benzyltoluene: Energy-efficient scale-up strategies and techno-economic analyses - In Seop Lim; Yoonseong Jeong; Yeonsu Kwak; Eui-Rim On; Quan Nguyen Dao; Hyangsoo Jeong; Hyuntae Sohn; Suk Woo Nam; Tae-Hoon Lim; Karsten Müller; Yongmin Kim (Chemical Engineering Journal, 2023)

Development of an In Vitro Model for Inflammation Mediated Renal Toxicity Using 3D Renal Tubules and Co-Cultured Human Immune Cells - Mi-lang Kyun; Tamina Park; Hyewon Jung; Inhye Kim; Ji-In Kwon; Seo Yule Jeong; Myeongjin Choi; Daeui Park; Yu Bin Lee; Kyoung-Sik Moon (Tissue Engineering and Regenerative Medicine, 2023)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Characterization and distribution of black rot disease causing pathogen-Xanthomonas campestris pv. campestris races of the Jeju Island, South Korea - Jeong-Eui Hong; Hee-Jin Kim; Mohammad Rashed Hossain; Mehede Hassan Rubel; Nihar Sahu; Sopheap Mao; Jong-Goo Kang; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of Plant Pathology, 2023)

Characterization and genomic insight of surfactin-producing Bacillus velezensis and its biocontrol potential against pathogenic contamination in lettuce hydroponics - Husna; Bo-Eun Kim; Myeong-Hee Won; Myeong-In Jeong; Kwang-Kyo Oh; Dong Suk Park (Environmental Science and Pollution Research, 2023)

Field experiments on chemical and biological changes of thin-layer oyster shells capping sediments in dense aquaculture area - Hee-Eun Woo; Ilwon Jeong; Jong-Oh Kim; Young-Ryun Kim; In-Cheol Lee; Kyunghoi Kim (Environmental Research, 2023)

Design strategy of cathodic electrocatalysts to effectively suppress inorganic fouling for long-term stability of reverse electrodialysis - Eunjin Jwa; Hanki Kim; Joo-Youn Nam; Jong-In Han; Namjo Jeong (Chemical Engineering Journal, 2023)

Microplastic contamination in groundwater of rural area, eastern part of Korea - Eunju Jeong; Young-In Kim; Jin-Yong Lee; Maimoona Raza (Science of The Total Environment, 2023)

Effect of pulsed electric field pretreatment on mass transfer during hot air drying: Drying and rehydration properties of sweet potato - Si-Yoen Kim; Ui-Chan Jeong; Hye-In Ju; Seho Jeong; Dong-Un Lee (Innovative Food Science & Emerging Technologies, 2023)

Quantification and health risk assessment of ochratoxin A in dried fruit, spices, and coffee - In Min Hwang; Ji Young Jeong; Boyeon Park; Ji Yeon Choi; Naeem Khan; Nargis Jamila; Bo Ryun Yoon; Jae Sung Kim (Food Additives & Contaminants: Part A, 2023)

Spatial distribution of meiofaunal and macrofaunal assemblages in the tidal flats of the southern Korean coast in relation to natural and anthropogenic impacts - Jeong Won Kim; Hyeong-Gi Kim; Hyein Kim; Stephen John Hawkins; In-Soo Seo; Chul-Woong Oh (Marine Pollution Bulletin, 2023)

Detection of microplastic traces in four different types of municipal wastewater treatment plants through FT-IR and TED-GC-MS - Jae-Ho Lee; Min-Jung Kim; Chang-Soo Kim; So-Jeong Cheon; Ki-In Choi; Juyang Kim; Jaehak Jung; Jeong-Ki Yoon; Soo-Hyung Lee; Dong-Hwan Jeong (Environmental Pollution, 2023)

First report on natural infection of Nepenthes alata by pepper mild mottle virus in Korea - Ga-Eun Lee; Hae-Jun Kim; In-Sook Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Environmental DNA surveillance of biocontamination in a drinking water treatment plant - Kyu-Young Shim; Heesang Shin; In-Cheol Yeo; Kyu Ri Kim; Ihn-Sil Kwak; Chang-Bum Jeong (Journal of Hazardous Materials, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Toxicological effects of tire rubber-derived 6PPD-quinone, a species-specific toxicant, and dithiobisbenzanilide (DTBBA) in the marine rotifer Brachionus koreanus - Usha Jyoti Maji; Kyuhyeong Kim; In-Cheol Yeo; Kyu-Young Shim; Chang-Bum Jeong (Marine Pollution Bulletin, 2023)

Maternal exposure to nanoplastic induces transgenerational toxicity in the offspring of rotifer Brachionus koreanus - In-Cheol Yeo; Kyu-Young Shim; Kyuhyeong Kim; Chang-Bum Jeong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Development and validation of an air recirculated ventilation system, Part 1: Application of system in a pig farm and evaluation of pig productivity during winter - Jun-gyu Kim; In-bok Lee; Andre Aarnink; Bong-joo Lee; Deuk-young Jeong; Hyo-hyeog Jeong; Se-han Kim; Bong-kuk Lee; Dong-kyu Lee (Biosystems Engineering, 2023)

Development and validation of an air recirculated ventilation system, Part 2: Evaluation of pig productivity in spring and summer seasons including examination of cooling methods - Jun-gyu Kim; In-bok Lee; Deuk-young Jeong; Se-jun Park; Jeong-hwa Cho; Rack-woo Kim (Biosystems Engineering, 2023)

Biochemical responses and phytoremediation potential of Azolla imbricata (Roxb.) Nakai in water and nutrient media exposed to waste metal cutting fluid along with temperature and humidity stress - Sivakumar Subpiramaniyam; Sung-Chul Hong; Pyong-In Yi; Seong-Ho Jang; Jeong-Min Suh; Eun-Sang Jung; Je-Sung Park; Velmurugan Palanivel; Young-Chae Song; Lae-Hyeon Cho; Young-Hoon Park; Ji-Suk Kim (Journal of Hazardous Materials, 2023)

Microplastic contamination in groundwater on a volcanic Jeju Island of Korea - Young-In Kim; Eunju Jeong; Jin-Yong Lee; Rogers Wainkwa Chia; Maimoona Raza (Environmental Research, 2023)

Unveiling reactive origin through the in situ 2D core–shell formation, Ni(CN)2@Ni2P, derived from Hofmann-type MOF for water oxidation - Jiwon Kim; Hyung Wook Choi; Jongseok Kim; Jung Hyeon Yoo; Dong In Jeong; Ui Young Lee; Hyuk Choi; Bong Kyun Kang; Ki-Seok An; Hyun You Kim; Dae Ho Yoon (Chemical Engineering Journal, 2023)

Correction to: Cerebral glucose metabolism differs according to future weight change - Jeong Mi Kim; Minhee Jang; Eun Heui Kim; Mijin Kim; Su Jung Choi; Keunyoung Kim; Kyoungjune Pak; Yun Kyung Jeon; Sang Soo Kim; Bo Hyun Kim; Seong-Jang Kim; In Joo Kim (Brain Imaging and Behavior, 2023)

Determination of the optimal location and the number of sensors for efficient heating, ventilation, and air conditioning system operation in a mechanically ventilated pig house - Uk-Hyeon Yeo; Sang-Yeon Lee; Se-Jun Park; Jun-Gyu Kim; Deuk-Young Jeong; Cristina S. Decano-Valentin; Rack-Woo Kim; In-Bok Lee (Biosystems Engineering, 2023)

Glucosinolates and Biotic Stress Tolerance in Brassicaceae with Emphasis on Cabbage: A Review - Md. Abuyusuf; Mehede Hassan Rubel; Hoy-Taek Kim; Hee-Jeong Jung; Ill-Sup Nou; Jong-In Park (Biochemical Genetics, 2023)

Estimation of ventilation rate in a piglet house considering ventilation system characteristics - Young-bae Choi; Jun-gyu Kim; Jeong-hwa Cho; Sang-yeon Lee; Se-jun Park; Cristina Decano-Valentin; Deuk-young Jeong; In-bok Lee (Biosystems Engineering, 2023)

Recycling of minerals with acetate separation in biological syngas fermentation with an electrodialysis system - Jae-Hun Kim; Mungyu Lee; Hoyoung Jeong; Songju Ko; Seung-Hyeon Moon; In Seop Chang (Chemical Engineering Journal, 2023)

Natural Variations in the Benthic Environment and Bacterial Communities of Coastal Sediments around Aquaculture Farms in South Korea - Maheshkumar Prakash Patil; Ilwon Jeong; Hee-Eun Woo; Jong-Oh Kim; Dae In Lee; Kyunghoi Kim (Indian Journal of Microbiology, 2023)

High-pressure induced structural modification of porcine myofibrillar protein and its relation to rheological and emulsifying properties - Min Hyeock Lee; Hae In Yong; Yun Jeong Kim; Yun-Sang Choi (Meat Science, 2023)

A highly efficient and versatile genetic engineering toolkit for a methanotroph-based biorefinery - Jiyeong Jeong; Tae Hyun Kim; Nulee Jang; Minji Ko; Seong Keun Kim; Ji In Baek; Georgii Emelianov; Eugene Rha; Kil Koang Kwon; Haseong Kim; Eun Yeol Lee; Dae-Hee Lee; et al. (Chemical Engineering Journal, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Stability and inactivation of SARS-CoV-2 on food contact surfaces - Soontag Jung; Dong-Hwi Kim; Hee-Seop Ahn; Hyeon-Jeong Go; Zhaoqi Wang; Daseul Yeo; Seoyoung Woo; Yeeun Seo; Md Iqbal Hossain; In-Soo Choi; Sang-Do Ha; Changsun Choi (Food Control, 2023)

Exposure to China dust exacerbates testicular toxicity induced by cyclophosphamide in mice - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Toxicological Research, 2023)

3-Hydroxymorphinan protects against hypoxia-induced cell death in primary astrocyte by regulating Ca2+ influx and the glutamate homeostasis - Ok-Hyeon Kim; Gyeong Yun Lee; Kyung Yong Kim; Jong In Son; Tae Woo Jung; Ji Hoon Jeong; Joon Seok Bang; Hyoung-Chun Kim; Yoon Hee Chung; Hyun Jung Lee (Molecular & Cellular Toxicology, 2023)

Description of Microbacterium neungamense sp. nov. isolated from a hot spring - Dariimaa Ganbat; Ga Eul Jeong; DoKyung Oh; Dong-Woo Lee; Yong-Jik Lee; Seong-Bo Kim; In-Tae Cha; Won-Jae Chi; Seul-Ki Park; Jung-Sook Lee; Sang-Jae Lee (Archives of Microbiology, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Display of Streptococcus iniae α-Enolase on the Surface of Virus-Like Particles (VLPs) of Nervous Necrosis Virus (NNV) Using SpyTag/SpyCatcher - Jeong In Yang; Ki Hong Kim (Marine Biotechnology, 2022)

Asian-specific 3’UTR variant in CDKN2B associated with risk of pituitary adenoma - Byeong Ju Youn; Hyun Sub Cheong; Suhg Namgoong; Lyoung Hyo Kim; In Ki Baek; Jeong-Hyun Kim; Seon-Jin Yoon; Eui Hyun Kim; Se Hoon Kim; Jong Hee Chang; Sun Ho Kim; Hyoung Doo Shin (Molecular Biology Reports, 2022)

Evaluation of genotoxicity of SUNACTIVE Zn-P240 in vitro and in vivo - Jeong-Hyun Lim; Jong-Yun Lee; Woong-Il Kim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Jong-Choon Kim (Toxicological Research, 2022)

Tomato ARPC1 regulates trichome morphology and density and terpene biosynthesis - Jae-In Chun; Seong-Min Kim; Na-Rae Jeong; Sang Hee Kim; Choonkyun Jung; Jin-Ho Kang (Planta, 2022)

Activation of galactose utilization by the addition of glucose for the fermentation of agar hydrolysate using Lactobacillus brevis ATCC 14869 - Godfrey Mwiti; In-Seok Yeo; Kyung-Hun Jeong; Hyung-Seok Choi; Jaehan Kim (Biotechnology Letters, 2022)

Subchronic Toxicity Evaluation of Aluminum Oxide Nanoparticles in Rats Following 28-Day Repeated Oral Administration - Sung-Hyeuk Park; Je-Oh Lim; Woong-Il Kim; So-Won Park; Se-Jin Lee; In-Sik Shin; Changjong Moon; Je-Hein Kim; Jeong-Doo Heo; Jong-Choon Kim (Biological Trace Element Research, 2022)

Persistent Continental Shelf Carbon Sink at the Ieodo Ocean Research Station in the Northern East China Sea - Kitack Lee; Ja-Myung Kim; Gyeong-Seok Lee; Eunil Lee; Jin-Yong Jeong; Jaeik Lee; In-Seong Han (Frontiers in Marine Science, 2022)
Hourly (2017–2021) to seasonal (2015–2021) inorganic C data were collected at the Ieodo Ocean Research Station (32.07°N and 125.10°E) in the northern East China Sea (ECS), located under the influence of the nutrient-rich Changjiang Diluted Water (CDW). An increase in phytoplankton biomass from April to mid-August (the warming period) equalized much of the temperature-driven increase in the surface pCO 2 and thus, made the northern ECS a moderate sink of atmospheric CO 2 . From November to March (the cooling period), a large pCO 2 reduction, driven by a temperature reduction, and a high air–sea CO 2 exchange rate, because of high windspeeds, transformed the basin into a substantial CO 2 sink, yielding an annual net C uptake of 61.7 g C m –2 yr –1 . The effects of biological production and temperature change on seawater pCO 2 (and thus, the net air–sea CO 2 flux) were decoupled each season and acted in concert to increase the net annual CO 2 sink by the region. The present study provided the observational and mechanistic lines of evidence for confirming “continental shelf C pump”—a mechanism in the shallow waters of the continental shelves that accumulate a significant amount of C ( via reinforced cooling and promoted biological C uptake) that is transported from the basin surface waters to the interior of the adjacent deep ocean. In the future, an increasing input of anthropogenic nutrients into the northern ECS is likely to make the region a stronger CO 2 sink.

A Comparative Study of an Anti-Thrombotic Small-Diameter Vascular Graft with Commercially Available e-PTFE Graft in a Porcine Carotid Model - Kyo Seon Lee; Mukhammad Kayumov; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Yun-Jin Jeong; Dong-Weon Lee; Jun-Kyu Park; Chan-Hee Park; Cheol-Sang Kim; Francis O. Obiweluozor; In-Seok Jeong (Tissue Engineering and Regenerative Medicine, 2022)
Background: We have designed a reinforced drug-loaded vascular graft composed of polycaprolactone (PCL) and polydioxanone (PDO) via a combination of electrospinning/3D printing approaches. To evaluate its potential for clinical application, we compared the in vivo blood compatibility and performance of PCL/PDO + 10%DY grafts doped with an antithrombotic drug (dipyridamole) with a commercial expanded polytetrafluoroethylene ( e -PTFE) graft in a porcine model. Methods: A total of 10 pigs (weight: 25–35 kg) were used in this study. We made a new 5-mm graft with PCL/PDO composite nanofiber via the electrospinning technique. We simultaneously implanted a commercially available e -PTFE graft ( n = 5) and our PCL/PDO + 10%DY graft ( n = 5) into the carotid arteries of the pigs. No anticoagulant/antiplatelet agent was administered during the follow-up period, and ultrasonography was performed weekly to confirm the patency of the two grafts in vivo . Four weeks later, we explanted and compared the performance of the two grafts by histological analysis and scanning electron microscopy (SEM). Results: No complications, such as sweating on the graft or significant bleeding from the needle hole site, were seen in the PCL/PDO + 10%DY graft immediately after implantation. Serial ultrasonographic examination and immunohistochemical analysis demonstrated that PCL/PDO + 10%DY grafts showed normal physiological blood flow and minimal lumen reduction, and pulsed synchronously with the native artery at 4 weeks after implantation. However, all e -PTFE grafts occluded within the study period. The luminal surface of the PCL/PDO + 10%DY graft in the transitional zone was fully covered with endothelial cells as observed by SEM. Conclusion: The PCL/PDO + 10%DY graft was well tolerated, and no adverse tissue reaction was observed in porcine carotid models during the short-term follow-up. Colonization of the graft by host endothelial and smooth muscle cells coupled with substantial extracellular matrix production marked the regenerative capability. Thus, this material may be an ideal substitute for vascular reconstruction and bypass surgeries. Long-term observations will be necessary to determine the anti-thrombotic and remodeling potential of this device.

Evaluation of residual level and distribution characteristics of organochlorine pesticides in agricultural soils in South Korea - Sung-Mi Yun; Jeong-ki Yoon; Ji-In Kim; In Ja Kim; Hyun-Koo Kim; Hyen-Mi Chung; Dong-Jin Kim; Hoe-Jung Noh (Environmental Science and Pollution Research, 2022)

Characterization of non-solvent- and thermal-induced phase separation applied polycaprolactone/demineralized bone matrix scaffold for bone tissue engineering - Soo in Kim; Na Eun Kim; Sunjae Park; Joo Hee Choi; Younghun Lee; Gayeong Jeon; Jeong Eun Song; Gilson Khang (In vitro models, 2022)

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Sacubitril/valsartan reduces endoplasmic reticulum stress in a rat model of doxorubicin-induced cardiotoxicity - Byung Sik Kim; In-Hwa Park; A-Hyeon Lee; Hyun-Jin Kim; Young-Hyo Lim; Jeong-Hun Shin (Archives of Toxicology, 2022)

Comparison of the pathogenicity of porcine reproductive and respiratory syndrome virus (PRRSV)-1 and PRRSV-2 in pregnant sows - Chang-Gi Jeong; Salik Nazki; Seung-Chai Kim; Amina Khatun; Yun-Hee Noh; Dong-Uk Lee; Sang Chul Kang; Byoung-Joo Seo; Myeon-Sik Yang; Sim-In Lee; In-Joong Yoon; Bumseok Kim; et al. (Archives of Virology, 2022)

Protective effect of berberine chloride against cisplatin-induced ototoxicity - Jong-Heun Kim; Jeong-In Baek; In-Kyu Lee; Un-Kyung Kim; Ye-Ri Kim; Kyu-Yup Lee (Genes & Genomics, 2022)
Background Cisplatin (CP) is an effective anticancer drug broadly used for various types of cancers, but it has shown ototoxicity that results from oxidative stress. Berberine has been reported for its anti-oxidative stress suggesting its therapeutic potential for many diseases such as colitis, diabetes, and vascular dementia. Objective Organ of Corti of postnatal day 3 mouse cochlear explants were used to compare hair cells after the treatment with cisplatin alone or with berberine chloride (BC) followed by CP. Methods We investigated the potential of the anti-oxidative effect of BC against the cisplatin-induced ototoxicity. We observed a reduced aberrant bundle of stereocilia in hair cells in CP with BC pre-treated group. Caspase-3 immunofluorescence and TUNEL assay supported the hypothesis that BC attenuates the apoptotic signals induced by CP. Reactive oxygen species level in the mitochondria were investigated by MitoSOX Red staining and the mitochondrial membrane potentials were compared by JC-1 assay. Results BC decreased ROS generation with preserved mitochondrial membrane potentials in mitochondria as well as reduced DNA fragmentation in hair cells. In summary, our data indicate that BC might act as antioxidant against CP by reducing the stress in mitochondria resulting in cell survival. Conclusion Our result suggests the therapeutic potential of BC for prevention of the detrimental effect of CP-induced ototoxicity.

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

In silico analysis and expression profiling revealed Rlm1′ blackleg disease-resistant genes in Chromosome 6 of Brassica oleracea - Arif Hasan Khan Robin; Gopal Saha; Jong-In Park; Rawnak Laila; Md Abdur Rahim; Mita Bagchi; Hoy-Taek Kim; Hee-Jeong Jung; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2021)

Increased Cysteine Accumulation is Essential for Salt Stress Tolerance in Arabidopsis Halotolerance 2-Like (AHL)-Overexpressing Transgenic Plants - Tinh Van Nguyen; Jeong-In Kim; Cho-Rong Park; Moon-Soo Chung; Cheol Soo Kim (Journal of Plant Biology, 2021)

Parasphingorhabdus halotolerans sp. nov. isolated from marine sediment in Jeju Island - So-Jeong Kim; Minji Kim; Ki-Eun Lee; In-Tae Cha; Soo-Je Park (Archives of Microbiology, 2021)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Removal of organochlorine insecticide endosulfan in water and soil by Fenton reaction with ascorbic acid and various iron resources - Jeong-In Hwang; Jang-Eok Kim (Environmental Science and Pollution Research, 2021)

Effect of different planting times on the quantitative variation of total seed isoflavone content and composition in Korean soybean cultivars (Glycine max (L.) Merr.) - Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Tae-Joung Ha; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
There is great interest in the enhancement of isoflavones as one of the functional ingredients in soybean. This study aimed to investigate the effects of changes in the ecological environment over different planting times on isoflavone content. A total of 28 Korean soybean cultivars were grown at different planting times in late May, mid-June, and early July and their isoflavone content was measured over 2 years (2017 and 2018). Analyses of variance revealed significant effects of genotypes, planting times, years, and their interactions on isoflavone content. The average content of total isoflavone, as well as its component groups of malonylglucoside and aglycon, increased significantly as the seed planting time was delayed from late May to early July. The accumulation of each isoflavone component varied with changes in the planting time. The isoflavone content of the soybean cultivars for soy-sprout and soy-paste and tofu were higher for plantings in early July than for those in late May and/or mid-June, except for the black soybean cultivars. Despite significant correlations of the isoflavone content of the 28 cultivars among the three planting times, the responses of individual cultivars varied in isoflavone content by planting time. When planting was delayed, the time to flowering and maturity was also delayed and the number of days of growth from planting or flowering to maturity decreased; however, this was not related to isoflavone content. When planting was delayed, the temperature during the ripening period from flowering to maturity was lower, which was inversely related to the isoflavone content.

Role of p53 in transcriptional repression of SVCT2 - Eun Ho Kim; Dong-In Koh; Yea Seong Ryu; Sang-Soo Park; Seung-Woo Hong; Jai-Hee Moon; Jae-Sik Shin; Mi Jin Kim; Do Yeon Kim; Jun Ki Hong; Hong-Rae Jeong; Hyeseon Yun; et al. (Molecular Biology Reports, 2021)

First report of tomato spotted wilt virus infecting Cirsium setidens in Korea - Seongmu Mun; Su-Yeon Hwang; Na-Kyeong Kim; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

Identification and characterization of carotenoid biosynthesis related genes in a novel dark skinned citrus mutant cultivar ‘Suneat’ - Md. Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2021)

Tomato hairless on stems mutant affects trichome development - Won-Ki Hong; Jae-In Chun; Na-Rae Jeong; Heejin Kim; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Analysis of differentially expressed genes in soybean leaf tissue of tolerant and susceptible cultivars under flooding stress revealed by RNA sequencing - Sanjeev K. Dhungana; Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
Flooding stress causes severe yield reduction in soybean worldwide. The development of stress-tolerant cultivars could be an effective measure to reduce the negative effects of flooding stress. Molecular information on the gene expression pattern of tolerant and susceptible genotypes under flooding stress could be valuable to improve the flooding tolerance in soybean. The objective of this study was to analyze the differentially expressed genes (DEGs) revealed by RNA sequencing in the soybean leaf tissues of tolerant (‘Paldalkong’ and ‘Danbaekkong’) and susceptible (‘NTS1116’) cultivars under flooding stress. Seedlings were grown in a well-watered condition up to the V1–V2 stage and flood-stressed by inundating ~ 10-cm water for 14 days. A total of 22,468 genes were differentially expressed in flood-stressed condition compared to the well-watered control condition, out of which 13,729, 13,405, and 13,160 were differentially expressed in ‘Paldalkong’, ‘Danbaekkong’, and ‘NTS1116’, respectively. A higher number of some of the flooding tolerance-related genes such as lipoxygenase, expansin, glutathione S-transferase, and sugar efflux transporter were up-regulated in the tolerant cultivars than in the susceptible cultivar. The number of some abscisic acid-related transcription factors of basic leucine zipper domain and myeloblastosis families was also higher in the tolerant cultivars than in the susceptible cultivar. The molecular information about the DEGs of tolerant and susceptible cultivars obtained in the present study could be valuable to improve the flooding tolerance in soybeans.

Cerebral glucose metabolism differs according to future weight change - Jeong Mi Kim; Minhee Jang; Eun Heui Kim; Mijin Kim; Su Jung Choi; Keunyoung Kim; Kyoungjune Pak; Yun Kyung Jeon; Sang Soo Kim; Bo Hyun Kim; Seong-Jang Kim; In Joo Kim (Brain Imaging and Behavior, 2020)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

In silico characterization and expression of disease-resistance-related genes within the collinear region of Brassica napus blackleg resistant locus LepR1′ in B. oleracea - Mostari Jahan Ferdous; Mohammad Rashed Hossain; Jong-In Park; Hoy-Taek Kim; Arif Hasan Khan Robin; Sathishkumar Natarajan; Manosh Kumar Biswas; Hee-Jeong Jung; Ill-Sup Nou (Journal of General Plant Pathology, 2020)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

In-silico identification and differential expression of putative disease resistance-related genes within the collinear region of Brassica napus blackleg resistance locus LepR2’ in Brassica oleracea - Mohammad Rashed Hossain; Mostari Jahan Ferdous; Jong-In Park; Arif Hasan Khan Robin; Sathishkumar Natarajan; Hee-Jeong Jung; Hoy-Taek Kim; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)
Blackleg disease, caused by Leptosphaeria maculans, greatly affects the production of cabbage ( Brassica oleracea ). However, definitive R-gene(s) are yet to be identified in this crop. In contrast, a number of R-loci have been identified in A- or B-genome crops. Identification of few resistant cabbage genotypes indicates the presence of R-genes in this C-genome crop. High ancestral synteny between Brassica genomes suggests that the collinear regions of known A- or B-genome R-loci may also contain functional R-genes in the C-genome. Strong resistance was observed in the cotyledons of cabbage inbred line SCNU-98 against two L. maculans isolates, 03–02 s and 00–100 s. We investigated the collinear region of the Brassica napus blackleg resistance locus LepR2’ in B. oleracea since both isolates of L. maculans contain corresponding avirulence genes. The locus was collinear to a 5.8 Mbp genomic segment of B. oleracea chromosome C09 containing 13 genes that have putative disease resistance-related domains. High expression of genes Bo9g117290 and Bo9g111510 against isolate 00–100 s, and high expression of genes Bo9g126150 and Bo9g111490 against both isolates in the resistant-line SCNU-98 indicate their putative roles in blackleg resistance, which remained to be functionally verified. This work enhances our understanding of R-gene-mediated resistance to blackleg in cabbage.

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

Considerations in the Development of Small-Diameter Vascular Graft as an Alternative for Bypass and Reconstructive Surgeries: A Review - Francis O. Obiweluozor; Gladys A. Emechebe; Do-Wan Kim; Hwa-Jin Cho; Chan Hee Park; Cheol Sang Kim; In Seok Jeong (Cardiovascular Engineering and Technology, 2020)

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Pesticide residues in vegetables and risk assessment for consumers in Korea during 2010–2014 - Yun-Jeong Yi; Hyo-Jee Joung; Jin-Young Kum; in-Sook Hwang; Mu Sang Kim (Food Additives & Contaminants: Part A, 2020)

Identification of the prion-related protein gene (PRNT) sequences in various species of the Cervidae family - In-Soon Roh; Yong-Chan Kim; Hyo-Jin Kim; Sae-Young Won; Min-Ju Jeong; Hae-Eun Kang; Hyun-Joo Sohn; Byung-Hoon Jeong (Molecular Biology Reports, 2020)

Physiochemical Changes in Lipid-rich Mackerel during the Preparation of Smoked Mold Ripened Meat Products - Joon-Young Jun; Min-Jeong Jung; Jun-Seok Kum; Gwang-Woo Kim; Jae-Hyung Jung; Jae-Man Sim; In-Hak Jeong; Byoung-Mok Kim (Journal of Aquatic Food Product Technology, 2020)

Pulmonary inflammation caused by silica dioxide nanoparticles in mice via TXNIP/NLRP3 signaling pathway - Je-Oh Lim; Je-Won Ko; Tae-Yang Jung; Woong-Il Kim; So-Won Pak; In-Sik Shin; Won-Kee Yun; Hyoung-Chin Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2020)

Accumulation characteristics of endosulfan soil residues in soybean and reduction in their phytoavailability by treatment with powdered activated carbon - Jeong-In Hwang; Patrick Christopher Wilson; Jang-Eok Kim (Environmental Science and Pollution Research, 2020)

4-MeO-PCP and 3-MeO-PCMo, new dissociative drugs, produce rewarding and reinforcing effects through activation of mesolimbic dopamine pathway and alteration of accumbal CREB, deltaFosB, and BDNF levels - Arvie Abiero; Chrislean Jun Botanas; Raly James Custodio; Leandro Val Sayson; Mikyung Kim; Hyun Jun Lee; Hee Jin Kim; Kun Won Lee; Youngdo Jeong; Joung-Wook Seo; In Soo Ryu; Yong Sup Lee; et al. (Psychopharmacology, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Molecular characterization of Acidovorax citrulli strain NIHHS15-280 causing bacterial fruit blotch disease in Korea and screening of resistance sources in melon - Md. Rafiqul Islam; Mohammad Rashed Hossain; Hoy-Taek Kim; Ujjal Kumar Nath; Md. Abuyusuf; Hee-Jeong Jung; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

Genome-wide analysis of spatiotemporal gene expression patterns during floral organ development in Brassica rapa - Soo In Lee; Muthusamy Muthusamy; Muhammad Amjad Nawaz; Joon Ki Hong; Myung-Ho Lim; Jin A. Kim; Mi-Jeong Jeong (Molecular Genetics and Genomics, 2019)

Brassica rapa expansin-like B1 gene (BrEXLB1) regulate growth and development in transgenic Arabidopsis and elicits response to abiotic stresses - Panneerselvam Krishnamurthy; Muthusamy Muthusamy; Jin A. Kim; Mi-Jeong Jeong; Soo In Lee (Journal of Plant Biochemistry and Biotechnology, 2019)

The medicinal mushroom Auricularia auricula - judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells - Young-Ji Choi; In-Sun Park; Mi-Hee Kim; Bora Kwon; Young-Moo Choo; Seung-Il Jeong; Kang-Yeol Yu; Chung Hyeon Choe; Jiyoung Kim (Natural Product Research, 2019)

Complete genome sequence of a novel reassortant H3N3 avian influenza virus - Tran Bac Le; Hey Kwon Kim; Hai Yen Le; Min-Chul Jeong; In-Kyu Kim; Dae Gwin Jeong; Sun-Woo Yoon (Archives of Virology, 2019)

A Yellow Sea Monitoring Platform and Its Scientific Applications - Yong Sun Kim; Chan Joo Jang; Jae Hoon Noh; Kyung-Tae Kim; Jae-Il Kwon; Yongchim Min; Jongmin Jeong; Jaeik Lee; In-Ki Min; Jae-Seol Shim; Do-Seong Byun; Jinkwon Kim; et al. (Frontiers in Marine Science, 2019)

Development of a marker for detection of Xanthomonas campestris pv. campestris races 1 and 2 in Brassica oleracea - Mehede Hassan Rubel; Sathishkumar Natarajan; Ujjal Kumar Nath; Michael Immanuel Jesse Denison; Jung Hee-Jeong; Kim Hoy-Taek; Park Jong-In; Nou Ill-Sup (Horticulture, Environment, and Biotechnology, 2019)

Gene Flow from Transgenic PPO-inhibiting Herbicide-resistant Rice to Weedy Rice, and Agronomic Performance by Their Hybrids - Kyong-Hee Nam; Do Young Kim; Ye Seul Moon; In Soon Pack; Soon-Chun Jeong; Kee Woong Park; Chang-Gi Kim (Journal of Plant Biology, 2019)

Multidrug-resistant Acinetobacter baumannii infection in lung transplant recipients: risk factors and prognosis - Dong Hyun Oh; Yong Chan Kim; Eun Jin Kim; In Young Jung; Su Jin Jeong; Song Yee Kim; Moo Suk Park; Anes Kim; Jin Gu Lee; Hyo Chae Paik (Infectious Diseases, 2019)

Elevated carbon dioxide significantly improves ascorbic acid content, antioxidative properties and restricted biomass production in cruciferous vegetable seedlings - Muthusamy Muthusamy; Jung Eun Hwang; Suk Hee Kim; Jin A. Kim; Mi-Jeong Jeong; Hyeong Cheol Park; Soo In Lee (Plant Biotechnology Reports, 2019)

Tsunami hazard from submarine landslides: scenario-based assessment in the Ulleung Basin, East Sea (Japan Sea) - Roger Urgeles; Jang-Jun Bahk; Sang-Hoon Lee; Senay Horozal; Deniz Cukur; Seong-Pil Kim; Gil-Young Kim; Sueng-Won Jeong; In-Kwon Um (Geosciences Journal, 2019)

Correction to: Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Combined Treatment with Low-Level Laser and rhBMP-2 Promotes Differentiation and Mineralization of Osteoblastic Cells under Hypoxic Stress - Jin-Ho Heo; Jeong-Hun Choi; In-Ryoung Kim; Bong-Soo Park; Yong-Deok Kim (Tissue Engineering and Regenerative Medicine, 2018)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Hymenobacter segetis sp. nov., isolated from soil - Leonid N. Ten; Soo Jeong Lim; Byung-Oh Kim; In-Kyu Kang; Hee-Young Jung (Archives of Microbiology, 2018)

Recent Primary Production and Small Phytoplankton Contribution in the Yellow Sea during the Summer in 2016 - Hyo Keun Jang; Jae Jung Kang; Jae Hyung Lee; Myungjoon Kim; So Hyun Ahn; Jin-Yong Jeong; Mi Sun Yun; In-Seong Han; Sang Heon Lee (Ocean Science Journal, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Inverse agonist of ERRγ reduces cannabinoid receptor type 1-mediated induction of fibrinogen synthesis in mice with a high-fat diet-intoxicated liver - Yaochen Zhang; Don-Kyu Kim; Yoon Seok Jung; Yong-Hoon Kim; Yong Soo Lee; Jina Kim; Won-IL Jeong; In-Kyu Lee; Sung Jin Cho; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2018)

Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Genome-wide Characterization of Brassica rapa Genes Encoding Serine/arginine-rich Proteins: Expression and Alternative Splicing Events by Abiotic Stresses - Eun Kyung Yoon; Panneerselvam Krishnamurthy; Jin A. Kim; Mi-Jeong Jeong; Soo In Lee (Journal of Plant Biology, 2018)

Improved dissipation kinetic model to estimate permissible pre-harvest residue levels of pesticides in apples - Jeong-In Hwang; Hyo-Young Kim; Sang-Hyeob Lee; Se-Yeon Kwak; Andrew R. Zimmerman; Jang-Eok Kim (Environmental Monitoring and Assessment, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Expression of anthocyanin biosynthesis-related genes reflects the peel color in purple tomato - Song-I Kang; Md Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Intercomparison of Terrestrial Carbon Fluxes and Carbon Use Efficiency Simulated by CMIP5 Earth System Models - Dongmin Kim; Myong-In Lee; Su-Jong Jeong; Jungho Im; Dong Hyun Cha; Sanggyun Lee (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Fisetin protects H9c2 cardiomyoblast cells against H2O2-induced apoptosis through Akt and ERK1/2 signaling pathways - Jeong Soo Lee; Ji-Sook Lee; Kyung Jae Cha; Dae-Eun Kim; Daye Lee; Sun Young Jung; Eun-Seok Park; In Sik Kim (Molecular & Cellular Toxicology, 2018)

Effects of backcrossing on quality of strawberry fruit - Sun Yi Lee; Seung Yu Kim; Dae Young Kim; Ho Jeong Jeong; In Seok Um; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Genetic analysis of the tomato inquieta mutant links the ARP2/3 complex to trichome development - Na-Rae Jeong; Heejin Kim; In-Taek Hwang; Gregg A. Howe; Jin-Ho Kang (Journal of Plant Biology, 2017)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Sound waves increases the ascorbic acid content of alfalfa sprouts by affecting the expression of ascorbic acid biosynthesis-related genes - Joo Yeol Kim; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2017)

Miocene fossil plants from the Eoil Basin (Gampo area), Gyeongju, Korea - Eun Kyoung Jeong; Hyun Joo Kim; Kazuhiko Uemura; In Sung Paik; Kyungsik Kim (Geosciences Journal, 2017)

Discovery of candidate genes for heterosis breeding in Brassica oleracea L. - Seung-Yeon Jeong; Nasar Uddin Ahmed; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Acta Physiologiae Plantarum, 2017)

Plant growth promoting effect of Bacillus amyloliquefaciens H-2-5 on crop plants and influence on physiological changes in soybean under soil salinity - Min-Ji Kim; Ramalingam Radhakrishnan; Sang-Mo Kang; Young-Hyun You; Eun-Ju Jeong; Jong-Guk Kim; In-Jung Lee (Physiology and Molecular Biology of Plants, 2017)

Recovery of renal function after administration of adipose-tissue-derived stromal vascular fraction in rat model of acute kidney injury induced by ischemia/reperfusion injury - Chunwoo Lee; Myoung Jin Jang; Bo Hyun Kim; Jin Young Park; Dalsan You; In Gab Jeong; Jun Hyuk Hong; Choung-Soo Kim (Cell and Tissue Research, 2017)

Generation of α-1,3-galactosyltransferase knocked-out transgenic cloned pigs with knocked-in five human genes - Dae-Jin Kwon; Dong-Hwan Kim; In-Sul Hwang; Dong-Ern Kim; Hyung-Joo Kim; Jang-Seong Kim; Kichoon Lee; Gi-Sun Im; Jeong-Woong Lee; Seongsoo Hwang (Transgenic Research, 2017)

Overexpression of the OsbZIP66 transcription factor enhances drought tolerance of rice plants - Suin Yoon; Dong-Keun Lee; In Jeong Yu; Youn Shic Kim; Yang Do Choi; Ju-Kon Kim (Plant Biotechnology Reports, 2017)

Clozapine Improves Memory Impairment and Reduces Aβ Level in the Tg-APPswe/PS1dE9 Mouse Model of Alzheimer’s Disease - Yura Choi; Ha Jin Jeong; Quan Feng Liu; Seung Tack Oh; Byung-Soo Koo; Yeni Kim; In-Won Chung; Yong Sik Kim; Songhee Jeon (Molecular Neurobiology, 2017)

Vibrio injenensis sp. nov., isolated from human clinical specimens - Jayoung Paek; Jeong Hwan Shin; Yeseul Shin; In-Soon Park; Hongik Kim; Joong-Ki Kook; Seok-Seong Kang; Dae-Soo Kim; Kun-Hyang Park; Young-Hyo Chang (Antonie van Leeuwenhoek, 2017)

2-(4-{2-[(phenylthio)acetyl]carbonohydrazonoyl}phenoxy)acetamide as a new lead compound for management of allergic rhinitis - Hee-Yun Kim; Sun-Young Nam; Jae-Bum Jang; Youngjin Choi; In-Cheol Kang; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2016)

Gene loss/retention and evolutionary pattern of ascorbic acid biosynthesis and recycling genes in Brassica rapa following whole genome triplication - Panneerselvam Krishnamurthy; Jin A. Kim; Mi-Jeong Jeong; Ill Sup Nou; Soo In Lee (Genes & Genomics, 2016)

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Reduction of GIGANTEA expression in transgenic Brassica rapa enhances salt tolerance - Jin A. Kim; Ha-eun Jung; Joon Ki Hong; Victor Hermand; C. Robertson McClung; Yeon-Hee Lee; Joo Yeol Kim; Soo In Lee; Mi-Jeong Jeong; Jungsun Kim; DaeJin Yun; WeoYeon Kim (Plant Cell Reports, 2016)

Mechanism of protection by diallyl disulfide against cyclophosphamide-induced spermatotoxicity and oxidative stress in rats - Sung-Hwan Kim; In-Chul Lee; Je-Won Ko; In-Sik Shin; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

Protective effects of garlic oil against 1,3-dichloro-2-propanol-induced hepatotoxicity: role of CYP2E1 and MAPKs - Je-Won Ko; Sung-Hyeuk Park; In-Chul Lee; Sang-Min Lee; In-Sik Shin; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Comparative study of BMP-2 alone and combined with VEGF carried by hydrogel for maxillary alveolar bone regeneration - Sook Kyoung Kim; Tae Hyung Cho; Jeong Joon Han; In Sook Kim; Yongdoo Park; Soon Jung Hwang (Tissue Engineering and Regenerative Medicine, 2016)

Chondrogenic potential and anti-senescence effect of hypoxia on canine adipose mesenchymal stem cells - Jienny Lee; Jeong Su Byeon; Keum Sil Lee; Na-Yeon Gu; Gyeong Been Lee; Hee-Ryang Kim; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2016)

Genome-Wide Classification and Abiotic Stress-Responsive Expression Profiling of Carotenoid Oxygenase Genes in Brassica rapa and Brassica oleracea - Yonguk Kim; Indeok Hwang; Hee-Jeong Jung; Jong-In Park; Jong-Goo Kang; Ill-Sup Nou (Journal of Plant Growth Regulation, 2016)

Transgenic Turfgrasses Expressing Hyperactive Ser599Ala Phytochrome A Mutant Exhibit Abiotic Stress Tolerance - Mayank Anand Gururani; Markkandan Ganesan; In-Ja Song; Yunjeong Han; Jeong-Il Kim; Hyo-Yeon Lee; Pill-Soon Song (Journal of Plant Growth Regulation, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Defining the RNA-binding glycine-rich (RBG) gene superfamily: new insights into nomenclature, phylogeny, and evolutionary trends obtained by genome-wide comparative analysis of Arabidopsis, Chinese cabbage, rice and maize genomes - Panneerselvam Krishnamurthy; Jin A Kim; Mi-Jeong Jeong; Chang Ho Kang; Soo In Lee (Molecular Genetics and Genomics, 2015)

Effective selection of soybean cultivars to wildfire disease pathogen Pseudomonas amygdali pv. tabaci - In Jeong Kang; Seung-Han Kim; Yong Weon Seo; Min Jeong Seo; Hyeong Kwon Shim; Dong Bum Shin; Sunggi Heu (Journal of Crop Science and Biotechnology, 2015)

Interpretation and estimation for dynamic mobility of chlorpyrifos in soils containing different organic matters - Jeong-In Hwang; Sung-Eun Lee; Jang-Eok Kim (Environmental Geochemistry and Health, 2015)

Enhancement of dissolution and bioavailability of ezetimibe by amorphous solid dispersion nanoparticles fabricated using supercritical antisolvent process - Eun-Sol Ha; Jeong-Soo Kim; In-hwan Baek; Sung-Joo Hwang; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2015)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Inhibition effect of phenyl compounds from the Oryza sativa roots on melanin production in murine B16-F10 melanoma cells - Jin-Gyeong Cho; Jeongran Huh; Rak-Hun Jeong; Byeong-Ju Cha; Sabina Shrestha; Dong-Geol Lee; Hee-Cheol Kang; Ji-Young Kim; Nam-In Baek (Natural Product Research, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Dopamine D4 receptors linked to protein kinase G are required for changes in dopamine release followed by locomotor activity after repeated cocaine administration - Jeong Hwan Oh; Dong Kun Lee; Yoon-Bo Shim; In Soo Ryu; Su Yeon Seo; Jieun Kim; Ju Hwan Yang; Hyun-Wook Cho; Eun Sang Choe (Experimental Brain Research, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Genome-wide analysis of the expansin gene superfamily reveals Brassica rapa-specific evolutionary dynamics upon whole genome triplication - Panneerselvam Krishnamurthy; Joon Ki Hong; Jin A Kim; Mi-Jeong Jeong; Yeon-Hee Lee; Soo In Lee (Molecular Genetics and Genomics, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

Manufacture of duck-beak bone particles with gamma-ray irradiation for bone graft - Se Eun Kim; Kyung Mi Shim; Seok Hwa Choi; Sung In Jeong; Jun Sik Son; Youn-Mook Lim; Seong Soo Kang (Tissue Engineering and Regenerative Medicine, 2014)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

ZnO nanoparticle induces apoptosis by ROS triggered mitochondrial pathway in human keratinocytes - Woo-In Ryu; Yoon-Hee Park; Hyun Cheol Bae; Jin Hee Kim; Sang Hoon Jeong; Hana Lee; Sang Wook Son (Molecular & Cellular Toxicology, 2014)

Isolation and characterization of polymorphic microsatellite markers from the Korean common squid Todarodes pacificus (Ommastrephidae) - Hye Suck An; Eun Mi Kim; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Phosphorylation of hypothalamic AMPK on serine485/491 related to sustained weight loss by alpha-lipoic acid in mice treated with olanzapine - Hyunjeong Kim; Minsun Park; Su-Kyoung Lee; Jihyeon Jeong; Kee Namkoong; Hyun-Sang Cho; Jin Young Park; Byung-In Lee; Eosu Kim (Psychopharmacology, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Genetic differences between broodstock and offspring of seven-band grouper in a hatchery - Hye Suck An; Jae Kwon Cho; Kyong Min Kim; Maeng Hyun Son; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Characterization of 22 polymorphic microsatellite markers for seven-band grouper Epinephelus septemfasciatus developed using a 454 pyrosequencing approach - Hye Suck An; Jae Kwon Cho; Kyong Min Kim; Maeng Hyun Son; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

Biocompatible Glycol Chitosan-Coated Gold Nanoparticles for Tumor-Targeting CT Imaging - In-Cheol Sun; Jin Hee Na; Seo Young Jeong; Dong-Eog Kim; Ick Chan Kwon; Kuiwon Choi; Cheol-Hee Ahn; Kwangmeyung Kim (Pharmaceutical Research, 2014)

Gene expression analysis reveals a functional role for the Ag-NPs-induced Egr-1 transcriptional factor in human keratinocytes - Gyeongmin Yoo; Sang Hoon Jeong; Woo In Ryu; Hana Lee; Jin Hee Kim; Hyun Cheol Bae; Sang Wook Son (Molecular & Cellular Toxicology, 2014)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Effects of strobe light stimulation on postnatal developing rat retina - Jung-a Shin; Eojin Jeong; In-Beom Kim; Hwa-young Lee (Experimental Brain Research, 2014)

Source Activation of P300 Correlates with Negative Symptom Severity in Patients with Schizophrenia - Do-Won Kim; Miseon Shim; Jeong-In Kim; Chang-Hwan Im; Seung-Hwan Lee (Brain Topography, 2014)

Development of freshwater sediment management standards for organic matters, nutrients, and metals in Korea - In Ae Huh; Yong Seok Kim; Soon Ju Yu; Stella Wong; Won Sik Shin; Hye Ok Park; Ho Jeong Kim; Hyun Woo Kim (Environmental Science and Pollution Research, 2014)

Metabolic versatility of toluene‐degrading, iron‐reducing bacteria in tidal flat sediment, characterized by stable isotope probing‐based metagenomic analysis - So‐Jeong Kim; Soo‐Je Park; In‐Tae Cha; Deullae Min; Jin‐Seog Kim; Won‐Hyung Chung; Jong‐Chan Chae; Che Ok Jeon; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary DNA stable isotope probing and metagenomic sequencing were used to assess the metabolic potential of iron‐reducing bacteria involved in anaerobic aromatic hydrocarbon degradation in oil spill‐affected tidal flats. In a microcosm experiment, 13 C‐toluene was degraded with the simultaneous reduction of F e( III )‐ NTA , which was also verified by quasi‐stoichiometric 13 C‐CO 2 release. The metabolic potential of the dominant member affiliated with the genus Desulfuromonas in the heavy DNA fraction was inferred using assembled scaffolds (designated TF genome, 4.40 Mbp with 58.8 GC mol%), which were obtained by Illumina sequencing. The gene clusters with peripheral pathways for toluene and benzoate conversion possessed the features of strict and facultative anaerobes. In addition to the class II ‐type benzoyl‐ CoA reductase ( B am) of strict anaerobes, the class I ‐type ( B cr) of facultative anaerobes was encoded. Genes related to the utilization of various anaerobic electron acceptors, including iron, nitrate (to ammonia), sulfur and fumarate, were identified. Furthermore, genes encoding terminal oxidases ( caa 3 , cbb 3 and bd ) and a diverse array of genes for oxidative stress responses were detected in the TF genome. This metabolic versatility may be an adaptation to the fluctuating availability of electron acceptors and donors in tidal flats.

Comparative study on the fauna composition of intertidal invertebrates between natural and artificial substrata in the northeastern coast of Jeju Island - Jae-Hoon Cha; Kwang-Bae Kim; Ji-Na Song; In-Soo Kim; Jeong-Bin Seo; Chul-Hwi Kwoun (Ocean Science Journal, 2013)

Chloroform induces HIF-1α-dependent VEGF expression in human keratinocytes - Jae Jun Nam; Hana Lee; Hyun Cheol Bae; Jinhee Kim; Sang Hoon Jeong; Woo-In Ryu; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Comparative genetic diversity of wild and hatchery-produced Pacific oyster (Crassostrea gigas) populations in Korea using multiplex PCR assays with nine polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Woo Jin Kim; Hyun Jeong Lim; Eun Mi Kim; Soon Gyu Byun; Young Baek Hur; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Desulfotomaculum tongense sp. nov., a moderately thermophilic sulfate-reducing bacterium isolated from a hydrothermal vent sediment collected from the Tofua Arc in the Tonga Trench - In-Tae Cha; Seong Woon Roh; So-Jeong Kim; Hee-Ji Hong; Hae-Won Lee; Wan-Taek Lim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Methanomethylovorans uponensis sp. nov., a methylotrophic methanogen isolated from wetland sediment - In-Tae Cha; Ui-Gi Min; So-Jeong Kim; Kyung June Yim; Seong Woon Roh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Natronomonas gomsonensis sp. nov., isolated from a solar saltern - Tae-Yoon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Man-Young Jung; Sang-A Lee; Seong Woon Roh; Kyung June Yim; Takashi Itoh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Perverted Head Impulse Test in Cerebellar Ataxia - Seong-Hae Jeong; Ji-Soo Kim; In Chul Baek; Jong Wook Shin; Hyunjin Jo; Ae Young Lee; Jae-Moon Kim (The Cerebellum, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Miocene Tilia (Malvaceae) woods in Korea: including a new taxon - Eun Kyoung Jeong; Kyungsik Kim; In Sung Paik; Jong-Deock Lim (Geosciences Journal, 2013)

Ionizing radiation-inducible microRNA miR-193a-3p induces apoptosis by directly targeting Mcl-1 - Jeong-Eun Kwon; Bu-Yeon Kim; Seo-Young Kwak; In-Hwa Bae; Young-Hoon Han (Apoptosis, 2013)

The relationship between antipsychotic D2 occupancy and change in frontal metabolism and working memory - Euitae Kim; Oliver D. Howes; Federico E. Turkheimer; Bo-Hyung Kim; Jae Min Jeong; Ji Who Kim; Jae Sung Lee; In-Jin Jang; Sang-Goo Shin; Shitij Kapur; Jun Soo Kwon (Psychopharmacology, 2013)

Hoeflea halophila sp. nov., a novel bacterium isolated from marine sediment of the East Sea, Korea - Man-Young Jung; Kee-Sun Shin; Suyeon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Mi-Na Kim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Effect of the size and surface charge of silica nanoparticles on cutaneous toxicity - Yoon-Hee Park; Hyun Cheol Bae; Yeonsue Jang; Sang Hoon Jeong; Ha Na Lee; Woo-In Ryu; Min Gun Yoo; Yu-Ri Kim; Meyoung-Kon Kim; Jong Kwon Lee; Jayoung Jeong; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

A novel COCH mutation associated with autosomal dominant nonsyndromic hearing loss disrupts the structural stability of the vWFA2 domain - Hyun-Ju Cho; Hong-Joon Park; Maria Trexler; Hanka Venselaar; Kyu-Yup Lee; Nahid G. Robertson; Jeong-In Baek; Beom Sik Kang; Cynthia C. Morton; Gert Vriend; László Patthy; Un-Kyung Kim (Journal of Molecular Medicine, 2012)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A molecular framework for risk assessment of a virus-tolerant transgenic pepper line - In Soon Pack; Yu-Jin Kim; Eun Soo Youk; Woo Kyu Lee; Won Kee Yoon; Kee Woong Park; Chang-Gi Kim; Chee Hark Harn; Hwan Mook Kim; Soon-Chun Jeong (Journal of Crop Science and Biotechnology, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

QTL analysis of fruit length using rRAMP, WRKY, and AFLP markers in chili pepper - Heung-Ryul Lee; Ki-Taek Kim; Hyoun-Joung Kim; Jung-Heon Han; Jeong-Ho Kim; Seon-In Yeom; Hyun Jung Kim; Won-Hee Kang; Jinxia-Shi; Soung-Woo Park; Ik-Hyun Bae; Semin Lee; et al. (Horticulture, Environment, and Biotechnology, 2011)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Allometric equations and biomass expansion factors of Japanese red pine on the local level - Choonsig Kim; Jaeyeob Jeong; Rae-Hyun Kim; Yeong-Mo Son; Kyeong Hak Lee; Jin-Seoung Kim; In-Hyeop Park (Landscape and Ecological Engineering, 2011)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Gene flow from herbicide-tolerant GM rice and the heterosis of GM rice-weed F2 progeny - Young Jin Chun; Dae In Kim; Kee Woong Park; Hyo-Jeong Kim; Soon-Chun Jeong; Ju Hee An; Kang Hyun Cho; Kyoungwhan Back; Hwan Mook Kim; Chang-Gi Kim (Planta, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

An improved method of protein isolation and proteome analysis with Saccharina japonica (Laminariales) incubated under different pH conditions - Eun-Young Kim; Dong-Gyun Kim; Yu-Ri Kim; Hye-Jung Hwang; Taek-Jeong Nam; In-Soo Kong (Journal of Applied Phycology, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Transformation of carotenoid biosynthetic genes using a micro-cross section method in kiwifruit (Actinidia deliciosa cv. Hayward) - Misun Kim; Seong-Cheol Kim; Kwan Jeong Song; Ho Bang Kim; In-Jung Kim; Eun-Young Song; Seung-Jong Chun (Plant Cell Reports, 2010)

Persistence of Genetically Modified Potatoes in the Field - Chang-Gi Kim; Do Young Kim; Ye Seul Moon; Hyo-Jeong Kim; Dae In Kim; Young Jin Chun; Kee Woong Park; Soon Chun Jeong; Soo Young Kim; Hwan Mook Kim (Journal of Plant Biology, 2010)

Characterization of chemical properties of atmospheric aerosols over Anmyeon (South Korea), a super site under Global Atmosphere Watch - Sung-Hwa Park; A. S. Panicker; Dong-In Lee; Woon-Seon Jung; Sang-Min Jang; Min Jang; Dongchul Kim; Yu-Won Kim; Harrison Jeong (Journal of Atmospheric Chemistry, 2010)

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Detection of replicating negative-sense RNAs in CaCo-2 cells infected with human astrovirus - So Young Jang; Weon Hwa Jeong; Mi Suk Kim; Young Min Lee; Jae In Lee; Gyu Cheol Lee; Soon Young Paik; Gwang Pyo Koh; Jong Min Kim; Chan Hee Lee (Archives of Virology, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Induction of Oxidative Stress in the Epididymis of Rats After Subchronic Exposure to Epichlorohydrin - In-Sik Shin; Jeong-Hyeon Lim; Sung-Hwan Kim; Kang-Hyeon Kim; Na-Hyeong Park; Chun-Sik Bae; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Woojin Jun; Jong-Choon Kim (Bulletin of Environmental Contamination and Toxicology, 2010)

Miocene woods of the Janggi Basin in Korea: Implications for paleofloral changes - Jong-Deock Lim; Eun-Kyoung Jeong; Kyungsik Kim; Mitsuo Suzuki; In Sung Paik; Haang-Mook Kim (Geosciences Journal, 2010)

Ailanthus altissima swingle has anti-anaphylactic effect and inhibits inflammatory cytokine expression via suppression of nuclear factor-kappaB activation - Tae-Hee Kang; In-Young Choi; Su-Jin Kim; Phil-Dong Moon; Jae-Uk Seo; Jae-Joong Kim; Nyeon-Hyung An; Sung-Hoon Kim; Min-Ho Kim; Jae-Young Um; Seung-Heon Hong; Hyung-Min Kim; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

AtObgC, a plant ortholog of bacterial Obg, is a chloroplast-targeting GTPase essential for early embryogenesis - Woo Young Bang; Akira Hata; In Sil Jeong; Tetsuya Umeda; Takayuki Masuda; Ji Chen; Ishizaki Yoko; I Nengah Suwastika; Dae Won Kim; Chak Han Im; Byung Hyun Lee; Yuno Lee; et al. (Plant Molecular Biology, 2009)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

Assessment of Gene Flow from Genetically Modified Anthracnose-Resistant Chili Pepper (Capsicum annuum L.) to a Conventional Crop - Chang-Gi Kim; Dae In Kim; Hyo-Jeong Kim; Ji Eun Park; Bumkyu Lee; Kee Woong Park; Soon-Chun Jeong; Kyung Hwa Choi; Joo Hee An; Kang-Hyun Cho; Young Soon Kim; Hwan Mook Kim (Journal of Plant Biology, 2009)

Inhibitory effect of immature plum on PMA-induced MMP-9 expression in human hepatocellular carcinoma - Mi Hee Yu; Hyo Gwon Im; Sung Gyu Lee; Dae-Ik Kim; Hwa Jeong Seo; In-Seon Lee (Natural Product Research, 2009)

Anti-Androgen Receptor Signaling and Prostate Cancer Inhibitory Effects of Sucrose- and Benzophenone-Compounds - Zhe Wang; Hyo-Jeong Lee; Lei Wang; Cheng Jiang; Nam-In Baek; Sung-Hoon Kim; Junxuan Lü (Pharmaceutical Research, 2009)

AGHR polymorphism and its associations with carcass traits in Harrwoo cattle - Sang-Hyun Han; In-Cheol Cho; Jin-Hyoung Kim; Moon-Suck Ko; Ha-Yeon Jeong; Hong-Shik Oh; Sung-Soo Lee (Genes & Genomics, 2009)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Effects of ethanol extract from Saururus chinensis (Bour.) Baill on lipid and antioxidant metabolisms in rats fed a high-fat diet - Mi Hee Yu; Hyo Gwon Im; Ji-Won Lee; Mi-Hyang Hwang Bo; Hyun-Jeong Kim; Suk Kyung Kim; Shin Kyo Chung; In-Seon Lee (Natural Product Research, 2008)

Detection of gene flow from GM to non-GM watermelon in a field trial - Chang-Gi Kim; Bumkyu Lee; Dae In Kim; Ji Eun Park; Hyo-Jeong Kim; Kee Woong Park; Hoonbok Yi; Soon-Chun Jeong; Won Kee Yoon; Chee Hark Harn; Hwan Mook Kim (Journal of Plant Biology, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Mechanism by whichBacillus-Derived 2-Aminobenzoic acid inhibits the growth ofArabidopsis thaliana Roots - Lam Hoang; Kyung Sik Song; In Koo Rhee; Jeong Hoe Kim; Sangman Lee (Journal of Plant Biology, 2007)

Determination of hypocentral parameters of local earthquakes using weighting factor based on take-off angle - In Kyeong Hahm; Woohan Kim; Jung Mo Lee; Jeong Soo Jeon (Geosciences Journal, 2007)

ENA Actimineral Resource A restores bone loss and bone quality in ovariectomized rats - Sun Hee Do; Sung-Yong Hwa; Won-Il Jeong; Ji-Won Lee; Hyun-Jung Kim; In-Seon Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

An α3β4 subunit combination acts as a major functional nicotinic acetylcholine receptor in male rat pelvic ganglion neurons - Kyu-Sang Park; Seung-Kyu Cha; Min-Jeong Kim; Dae-Ran Kim; Seong-Woo Jeong; Joong-Woo Lee; In Deok Kong (Pflügers Archiv - European Journal of Physiology, 2006)

Constitutive expression of two pathogenesis-related genes in tomato plants enhanced resistance to oomycete pathogen Phytophthora capsici - Sujon Sarowar; Young Jin Kim; Eui Nam Kim; Ki Deok Kim; Jun Young Choi; Nam In Hyung; Jeong Sheop Shin (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Monitoring the occurrence of genetically modified soybean and maize around cultivated fields and at a grain receiving port in Korea - Chang-Gi Kim; Hoonbok Yi; Sangkyu Park; Ji Eun Yeon; Do Young Kim; Dae In Kim; Kyu-Hwa Lee; Taek Chang Lee; In Soon Paek; Won Kee Yoon; Soon-Chun Jeong; Hwan Mook Kim (Journal of Plant Biology, 2006)

Cyclic diarylheptanoids inhibit cell-mediated low-density lipoprotein oxidation - Hyun-Mi Kang; Ju Ryong Kim; Tae-Sook Jeong; Sung-Gyu Choi; Young-Han Ryu; Goo Taeg Oh; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)

Injectable Polysaccharide Microcapsules for Prolonged Release of Minocycline for the Treatment of Periodontitis - Yoon Jeong Park; Jue Yeon Lee; Hey Ri Yeom; Kyung Hwa Kim; Sang Chul Lee; In Kyoung Shim; Chong Pyoung Chung; Seung Jin Lee (Biotechnology Letters, 2005)

Fractal Stochastic Modeling of Spiking Activity in Suprachiasmatic Nucleus Neurons - Sung-IL Kim; Jaeseung Jeong; Yongho Kwak; Yang In Kim; Seung Hun Jung; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

Dynamical Heterogeneity of Suprachiasmatic Nucleus Neurons Based on Regularity and Determinism - Jaeseung Jeong; Yongho Kwak; Yang In Kim; Kyoung J. Lee (Journal of Computational Neuroscience, 2005)

p53 and cell-cycle-regulated protein expression in small intestinal cells after fast-neutron irradiation in mice - Young-Heun Jee; Won-Il Jeong; Tae-Hwan Kim; In-Sun Hwang; Mee-Jung Ahn; Hong-Gu Joo; Su-Hyung Hong; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2005)

Transforming Growth Factor (TGF)-β1 Releasing Tricalcium Phosphate/Chitosan Microgranules as Bone Substitutes - Jue-Yeon Lee; Yang-Jo Seol; Kyoung-Hwa Kim; Yong-Moo Lee; Yoon-Jeong Park; In-Chul Rhyu; Chong-Pyoung Chung; Seung-Jin Lee (Pharmaceutical Research, 2004)

Modulatory Properties of Various Natural Chemopreventive Agents on the Activation of NF-κB Signaling Pathway - Woo-Sik Jeong; In-Wha Kim; Rong Hu; Ah-Ng Tony Kong (Pharmaceutical Research, 2004)

Modulation of AP-1 by Natural Chemopreventive Compounds in Human Colon HT-29 Cancer Cell Line - Woo-Sik Jeong; In-Wha Kim; Rong Hu; Ah-Ng Tony Kong (Pharmaceutical Research, 2004)

Subcellular accumulation of Cu in the Antarctic bivalve Laternula elliptica from a naturally Cu-elevated bay of King George Island - Heeseon J. Choi; In-Young Ahn; Ko-Woon Kim; Yong-Suk Lee; In-Sook Lee; Kye-Heon Jeong (Polar Biology, 2003)

Polysaccharide-enriched fraction isolated from Duchesnea chrysantha protects against oxidative damage - In Gyu Kim; Il Lae Jung; Tae Jeong Oh; Kug Chan Kim; Hae Won Shim (Biotechnology Letters, 2002)

Some confierous fossil woods from the Cretaceous of Korea - Kyungsik Kim; Eun Kyoung Jeong; Mitsuo Suzuki; Min Huh; In Sung Paik (Geosciences Journal, 2002)

Thidiazuron required for efficient somatic embryogenesis from suspension-cultured cells ofPimpinella brachycarpa - Joon Chul Kim; Mi Young Chang; Su In Son; Su Jeong Heo (Journal of Plant Biology, 2001)

Purification and biochemical characterization of a fibrinolytic enzyme from Bacillus subtilis BK-17 - Yong Kee Jeong; Jeong Uck Park; Hyun Baek; Sung Hoon Park; In Soo Kong; Dong Wan Kim; Woo Hong Joo (World Journal of Microbiology and Biotechnology, 2001)

Electricity production in biofuel cell using modified graphite electrode with Neutral Red - Doo Hyun Park; Si Kyoon Kim; In Ho Shin; Yoo Jung Jeong (Biotechnology Letters, 2000)

A shoot regeneration protocol effective on diverse genotypes of sunflower (Helianthus annuus L.) - Dong-Ho Shin; Jin Sook Kim; In Jeong Kim; Jaemo Yang; Soo Kyung Oh; Gab Chae Chung; Kyung-Hwan Han (In Vitro Cellular & Developmental Biology - Plant, 2000)

Stimulation of β-carotene synthesis by hydrogen peroxide in Blakeslea trispora - Jae-Cheol Jeong; In-Young Lee; Seon-Won Kim; Young-Hoon Park (Biotechnology Letters, 1999)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)